Resin composition and method for manufacturing the same

JP2025001935APending Publication Date: 2025-01-09ASAHI KASEI KOGYO KABUSHIKI KAISHA

Patent Information

Application Number
JP2023101737
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2025-01-09

AI Technical Summary

Benefits of technology

【0008】 本発明の一態様によれば、極めて高度な機械特性を有する樹脂組成物及びその製造方法が提供され得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001935000021
    Figure 2025001935000021
  • Figure 2025001935000001
    Figure 2025001935000001
  • Figure 2025001935000002
    Figure 2025001935000002
Patent Text Reader

Abstract

To provide: a resin composition having extremely high mechanical characteristic; and a method for manufacturing the resin composition.SOLUTION: One embodiment provides: a resin composition including a cellulose nanofiber, a thermoplastic resin, and a polyphenylene ether whose glass transition temperature by differential scanning calorimetry (DSC) is -100°C to 50°C, as well as a molded product, a molding material for 3D printing, and a formed object. In one embodiment, the polyphenylene ether has a saturated or unsaturated hydrocarbon group which may be substituted and has a carbon number of 7-25.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition containing cellulose nanofibers and a method for producing the same. [Background technology]

[0002] Resin materials are light and have excellent processing properties, and are therefore widely used in many fields, such as automobile parts, electrical and electronic parts, office equipment housings, and precision parts. However, resin alone often has insufficient mechanical properties and dimensional stability, so composites of resin and various fillers are generally used. In recent years, the use of cellulose nanofibers (CNFs), which are natural materials, as such fillers has been considered. CNFs have the advantage of having excellent mechanical properties while being environmentally friendly, but due to their fine structure, they tend to aggregate easily in a dry state, so they are manufactured as a dispersion liquid that allows stable dispersion. For example, when applying cellulose nanofibers to various applications, the above-mentioned dispersion liquid may be directly mixed with a resin, or the dispersion liquid may be dried and then dispersed in a dispersion medium or mixed with a resin in its dried form. However, in cellulose nanofibers, aggregation due to hydrogen bonds between cellulose molecules is extremely strong, so various methods have been proposed to suppress the aggregation of cellulose nanofibers.

[0003] For example, Patent Document 1 describes a dispersion for cellulose nanofibers that can disperse cellulose nanofibers without agglomerating them, the dispersion containing (A) a surface treatment agent that is a water-soluble polymer having hydrophilic and hydrophobic segments and a number average molecular weight of 200 to 30,000, (B) polyurethane, and water. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-063408 A Summary of the Invention [Problem to be solved by the invention]

[0005] The properties required of resin compositions containing cellulose nanofibers are becoming more advanced year by year, and in particular, molded articles obtained by molding resin compositions are now required to have a higher degree of dispersion of cellulose nanofibers, specifically, both a micrometer-scale dispersion that contributes to toughness and impact properties, and a nanometer-scale dispersion that contributes to rigidity and strength. The technology described in Patent Document 1 aims to increase the dispersibility of cellulose nanofibers by using a dispersion liquid containing a specific water-soluble polymer and polyurethane, but there is still room for improvement in providing resin compositions in which cellulose nanofibers are more highly dispersed.

[0006] An object of one aspect of the present invention is to solve the above problems and to provide a resin composition having extremely high mechanical properties and a method for producing the same. [Means for solving the problem]

[0007] This disclosure encompasses the following items. [1] A resin composition comprising cellulose nanofibers, a thermoplastic resin, and a polyphenylene ether having a glass transition temperature of -100°C to 50°C as measured by differential scanning calorimetry (DSC). [2] 2. The resin composition according to item 1, wherein the polyphenylene ether has an optionally substituted saturated or unsaturated hydrocarbon group having 7 to 25 carbon atoms. [3] 3. The resin composition according to item 1 or 2, wherein the polyphenylene ether contains a repeating unit derived from a phenol compound represented by the following formula (1): [ka] (In formula (1), R 13 is an optionally substituted saturated or unsaturated hydrocarbon group having 15 carbon atoms, R 11 and R 12 are each independently a hydrogen atom, a linear saturated hydrocarbon group having 1 to 12 carbon atoms, or a substituent represented by the following formula (1-1), where R 11 and R 12 None of the are hydrogen atoms.) [ka] (In formula (1-1), R 31 are each independently an optionally substituted linear alkyl group having 1 to 8 carbon atoms, or two R 31 The atoms in R are bonded to each other to form a cyclic alkyl group having 1 to 8 carbon atoms. 32 each independently represents an optionally substituted alkylene group having 1 to 8 carbon atoms; each b independently represents 0 or 1; R 33 is a hydrogen atom, an optionally substituted alkyl group having 1 to 8 carbon atoms, or an optionally substituted phenyl group. [4] R in the above formula (1) 11 is a substituent represented by formula (1-1). [5] 4. The resin composition according to item 3, wherein the substituent represented by formula (1-1) is a t-butyl group. [6] 6. The resin composition according to any one of items 1 to 5, wherein the polyphenylene ether has a weight average molecular weight of 1,000 to 150,000. [7] 7. The resin composition according to any one of items 1 to 6, wherein the polyphenylene ether has a viscosity at 80° C. of 1 mPa·s to 1,000,000 mPa·s. [8] 8. The resin composition according to any one of items 1 to 7, wherein the polyphenylene ether has a thermal decomposition onset temperature of 300° C. or higher. [9] 9. The resin composition according to any one of items 1 to 8, wherein the cellulose nanofibers are chemically modified cellulose nanofibers.

[10] Item 10. The resin composition according to item 9, wherein the chemically modified cellulose nanofibers are acylated cellulose nanofibers having an acyl substitution degree of 0.1 to 2.0.

[11] 11. The resin composition according to any one of items 1 to 10, wherein the cellulose nanofibers have a number average fiber diameter of 2 nm to 1000 nm.

[12] 12. The resin composition according to any one of items 1 to 11, wherein the cellulose nanofibers have a thermal decomposition onset temperature of 250° C. or higher.

[13] 13. The resin composition according to any one of items 1 to 12, wherein the polyphenylene ether is present in a state in which it has penetrated at least a part of the interface between the cellulose nanofibers and the thermoplastic resin.

[14] 14. The resin composition according to any one of items 1 to 13, wherein the resin composition has a weight loss rate at 250° C. of 1.5% or less.

[15] The thermal decomposition onset temperature T1 of the polyphenylene ether and the thermal decomposition onset temperature T2 of the cellulose nanofibers have the following relationship: (T1) ≧ (T2) 15. The resin composition according to any one of items 1 to 14,

[16] Item 16. The resin composition according to item 15, wherein the difference T1-T2 between T1 and T2 is 5°C or more.

[17] 17. The resin composition according to any one of items 1 to 16, wherein the thermoplastic resin is at least one selected from the group consisting of polyamide-based resins, polyolefin-based resins, and polyacetal-based resins.

[18] The thermal decomposition starting temperature T1 of the polyphenylene ether and the temperature T3 which is the melting point or the glass transition temperature + 70° C. of the thermoplastic resin satisfy the following relationship: (T1)>(T3) 18. The resin composition according to any one of items 1 to 17,

[19] Item 19. The resin composition according to item 18, wherein the thermoplastic resin is a thermoplastic resin having crystallinity, and the temperature T3 is a melting point of the thermoplastic resin.

[20] The thermal decomposition starting temperature T1 of the polyphenylene ether and the temperature T4 which is the melting point or the glass transition temperature + 100° C. of the thermoplastic resin satisfy the following relationship: (T1)>(T4) 20. The resin composition according to any one of items 1 to 19, which satisfies the above. [twenty one] 21. The resin composition according to any one of items 1 to 20, which is free of a surfactant. [twenty two] A dried body comprising cellulose nanofibers and polyphenylene ether having a glass transition temperature of -100°C to 50°C as measured by differential scanning calorimetry (DSC). [twenty three] A method for producing a resin composition according to any one of items 1 to 21, A method comprising heating and kneading a mixture containing cellulose nanofibers, a thermoplastic resin, and a polyphenylene ether having a glass transition temperature of -100°C to 50°C as measured by differential scanning calorimetry (DSC). [twenty four] A dried body containing cellulose nanofibers and polyphenylene ether having a glass transition temperature of -100°C to 50°C as measured by differential scanning calorimetry (DSC); A thermoplastic resin; 24. The method according to claim 23, wherein the mixture is obtained by mixing the above. [twenty five] 22. A molded article obtained by molding the resin composition according to any one of items 1 to 21.

[26] 26. The molded article according to item 25, which is a profile extrusion molded article.

[27] A method for producing a profile extrusion product, comprising: 22. A method comprising a step of profile extruding the resin composition according to any one of items 1 to 21.

[28] A 3D printing modeling material comprising the resin composition according to any one of items 1 to 21.

[29] Item 29. The 3D printing modeling material according to item 28, having the form of a filament or powder.

[30] A molded object obtained by molding the resin composition according to any one of items 1 to 21 or the 3D printing material according to item 28 or 29 using a 3D printer.

[31] A method for manufacturing a shaped object, comprising the steps of: A method comprising a step of modeling a resin composition according to any one of items 1 to 21 or a 3D printing material according to item 28 or 29 using a 3D printer. Effect of the Invention

[0008] According to one aspect of the present invention, a resin composition having extremely high mechanical properties and a method for producing the same can be provided. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a diagram showing the cross-sectional shape of a die of a single-screw extruder used in Examples 19 to 21. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The following is a detailed description of exemplary embodiments of the present invention (hereinafter, also referred to as the present embodiment), but the present invention is not limited to these embodiments. Note that, unless otherwise specified, the characteristic values ​​of the present disclosure are values ​​measured by the method described in the [Examples] section of the present disclosure or a method that is understood to be equivalent to the method by a person skilled in the art.

[0011] <Resin composition and dried body> A resin composition according to an embodiment of the present invention includes cellulose nanofibers, a thermoplastic resin, and polyphenylene ether. A dried body according to an embodiment of the present invention includes cellulose nanofibers and polyphenylene ether. In one embodiment, the polyphenylene ether is a polyphenylene ether having a glass transition temperature of −100° C. to 50° C. as measured by differential scanning calorimetry (DSC) (also referred to as low Tg polyphenylene ether in the present disclosure).

[0012] Polyphenylene ether is a polymer having an aromatic ring in its main chain, and therefore, unlike, for example, non-polymer materials (e.g., non-polymer surfactants) and polymers not having an aromatic ring in their main chain, it exhibits extremely high heat resistance and hydrophobicity that suppresses the aggregation of cellulose nanofibers and disperses the cellulose nanofibers to an extremely high degree in resin. The glass transition temperature of polyphenylene ether being in a relatively low range is advantageous from the viewpoint of improving the fluidity of polyphenylene ether and obtaining a good effect of suppressing the aggregation of cellulose nanofibers.

[0013] While cellulose nanofibers are essentially hydrophilic due to their hydroxyl groups, the properties of the resins that are combined with the cellulose nanofibers to form the resin composition vary depending on the type of resin selected. It is not easy to disperse cellulose nanofibers well in a wide variety of resins, and methods such as combining surfactants are used. However, surfactants are prone to thermal degradation due to heating when producing a resin composition (typically when cellulose nanofibers and resins are heated and kneaded) and heating when processing the resin composition to form various molded products, and products generated by such thermal degradation may remain in the resin composition or molded product and reduce mechanical properties. The present inventors have investigated various methods for achieving good dispersion of cellulose nanofibers in a wide variety of resins while eliminating the use of components that are prone to thermal degradation during the production and processing of the resin composition as much as possible. As a result, it has been found that polyphenylene ethers that have fluidity even at relatively low temperatures, more specifically, the low Tg polyphenylene ethers disclosed herein, can be combined with cellulose nanofibers to enable desired dispersion of cellulose nanofibers. Low Tg polyphenylene ethers have excellent fluidity while also tending to have superior thermal stability compared to non-polymeric surfactants and the like, and are therefore advantageous in that the mechanical properties of the resin composition and molded articles are not adversely affected even when the resin composition is subjected to heat during production and processing.

[0014] In a preferred embodiment, the low Tg polyphenylene ether is present in a form in which it has penetrated (i.e., has penetrated into) at least a part of the interface between the cellulose nanofiber and the resin. In the present disclosure, the form in which the low Tg polyphenylene ether has penetrated at least a part of the interface between the cellulose nanofiber and the resin means that the low Tg polyphenylene ether is observed at the interface between the cellulose nanofiber and the resin when the cellulose nanofiber, the resin, and the low Tg polyphenylene ether are distinguished by means such as staining in morphological observation using a scanning electron microscope and / or a transmission electron microscope. Such low Tg polyphenylene ether contributes to good dispersion of the cellulose nanofiber in the resin by being interposed between the cellulose nanofiber and the resin. The low Tg polyphenylene ether does not have to cover the entire surface of the cellulose nanofiber, but may preferably cover the entire surface.

[0015] <Cellulose nanofiber> The cellulose nanofiber may be obtained from various cellulose fiber raw materials selected from natural cellulose and regenerated cellulose. As the natural cellulose, wood pulp obtained from wood species (broadleaf or coniferous), non-wood pulp obtained from non-wood species (cotton, bamboo, hemp, bagasse, kenaf, cotton linters, sisal, straw, etc.), and cellulose fiber aggregates produced by animals (e.g., sea squirts), algae, and microorganisms (e.g., acetic acid bacteria) can be used. As the regenerated cellulose, regenerated cellulose fibers (viscose, cupra, Tencel, etc.), cellulose derivative fibers, and ultrafine threads of regenerated cellulose or cellulose derivatives obtained by electrospinning can be used. These raw materials can be adjusted, as necessary, by mechanical beating, fibrillation, and refinement using a grinder, refiner, etc. to adjust the fiber diameter, fiber length, fibrillation degree, etc., or by bleaching and refining using chemicals to adjust the content of components other than cellulose (acid-insoluble components such as lignin, alkali-soluble polysaccharides such as hemicellulose, etc.).

[0016] Cellulose nanofibers can be obtained by mechanically pulverizing cellulose raw materials in a dry or wet manner. This pulverization process can be carried out using a single device one or more times, or multiple devices can be used one or more times each. The equipment used for the pulp milling is not particularly limited, and examples thereof include high-speed rotation, colloid mill, high-pressure, roll mill, and ultrasonic types of equipment. Examples of equipment that can be used include high-pressure or ultra-high-pressure homogenizers, refiners, beaters, PFI mills, kneaders, dispersers, high-speed defibrators, grinders (stone-type grinders), ball mills, vibration mills, bead mills, conical refiners, disk-type refiners, single-axis, twin-axis, or multi-axis kneaders / extruders, homomixers under high-speed rotation, refiners, defibrators, beaters, friction grinders, high-shear fibrilators (e.g., Cavitron rotor / starter devices), dispergers, and homogenizers (e.g., microfluidizers), which act on pulp fibers with a metal or blade around a rotating shaft, or which use friction between pulp fibers themselves.

[0017] In one embodiment, the cellulose nanofibers can be obtained as a slurry, which can be prepared by dispersing and finely pulverizing cellulose fiber raw materials in water and / or other media (e.g., organic solvents, inorganic acids, bases, and / or ionic liquids).

[0018] The organic solvent used in the above-mentioned microparticulation treatment is not particularly limited, and examples thereof include alcohols having 1 to 20 carbon atoms, preferably 1 to 4 carbon atoms, such as methanol, ethanol, and propanol; glycol ethers having 2 to 20 carbon atoms, preferably 2 to 6 carbon atoms, such as methyl cellosolve and propylene glycol monomethyl ether; ethers having 2 to 20 carbon atoms, preferably 2 to 8 carbon atoms, such as propylene glycol monomethyl ether, 1,2-dimethoxyethane, diisopropyl ether, tetrahydrofuran, and 1,4-dioxane; acetone, methyl ethyl ketone, methyl Examples of the solvent include ketones having 3 to 20 carbon atoms, preferably 3 to 6 carbon atoms, such as ethyl isobutyl ketone; linear or branched saturated or unsaturated hydrocarbons having 1 to 20 carbon atoms, preferably 1 to 8 carbon atoms; aromatic hydrocarbons such as benzene and toluene; halogenated hydrocarbons such as methylene chloride and chloroform; carboxylic acids having 1 to 20 carbon atoms, such as formic acid, acetic acid, and lactic acid; esters having 2 to 20 carbon atoms, preferably 2 to 6 carbon atoms, such as ethyl acetate and vinyl acetate; nitrogen-containing solvents such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone, and sulfur-containing solvents such as dimethylsulfoxide. These can be used alone or in combination of two or more kinds, but from the viewpoint of operability of the microparticulation treatment, alcohols having 1 to 6 carbon atoms, glycol ethers having 2 to 6 carbon atoms, ethers having 2 to 8 carbon atoms, ketones having 3 to 6 carbon atoms, lower alkyl ethers having 2 to 5 carbon atoms, carboxylic acids having 1 to 8 carbon atoms, esters having 2 to 6 carbon atoms, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, dimethylsulfoxide, and the like are preferred.

[0019] Examples of inorganic acids include hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, boric acid, etc., but from the viewpoint of defibration efficiency and handling, preferably, one or more acids selected from the group consisting of hydrochloric acid, sulfuric acid, and phosphoric acid are used.

[0020] Examples of bases include hydroxides such as sodium hydroxide, potassium hydroxide, calcium hydroxide, etc., carbonates such as sodium carbonate, potassium carbonate, calcium carbonate, etc., ammonia, and organic amines such as triethylamine and triethanolamine, but from the viewpoints of defibration efficiency and handleability, one or more types selected from the group consisting of hydroxides, carbonates, and organic amines are preferred.

[0021] In the present disclosure, an ionic liquid refers to a liquid salt containing an organic ion in at least one of the cation moiety and the anion moiety, and the melting point of the ion alone is 100° C. or less. The cation moiety of the ionic liquid preferably has at least one cation selected from the group consisting of imidazolium cation, pyrrolidinium cation, piperidinium cation, morpholinium cation, pyridinium cation, quaternary ammonium cation, and phosphonium cation.

[0022] Among them, ionic liquids having an imidazolium skeleton, for example, ionic liquids having the following formula (I): [ka] (In the formula, R1 and R2 each independently represent an alkyl group or an allyl group having 1 to 8 carbon atoms, and X represents an anion.) The imidazolium-based ionic liquid represented by the formula (I) is more preferable in that it has a relatively lower melting point than other ionic liquids, exists in a liquid state over a wide temperature range, has fluidity even at low temperatures, and is excellent in thermal stability. From the viewpoint of defibration property, the number of carbon atoms in R1 and R2 is more preferably 4 or less, further preferably 3 or less, and most preferably 2 or less.

[0023] The anion components are halide ions (Cl - , Br - , I - etc.), carboxylate anions (e.g., carboxylate anions with a total of 1 to 3 carbon atoms, e.g., C2H5CO2 - , CH3CO2 - , HCO2 -etc.), pseudohalide ions (i.e., ions that are monovalent and have properties similar to those of halide ions, e.g., CN - , SCN - , OCN - , O.N.C. - , N3 - Examples of anions that can be used include anions of sulfonate, organic sulfonate (e.g., methanesulfonate), phosphate (e.g., ethyl phosphate, methyl phosphate, hexafluorophosphate), borate (e.g., tetrafluoroborate), and perchlorate, and from the viewpoint of defibration ability, halide ions and carboxylate anions are preferred.

[0024] Examples of imidazolium ionic liquids include 1-ethyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium formate, 1-allyl-3-methylimidazolium chloride, 1-allyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium dimethyl phosphate, 1-butyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium diethyl phosphate, 1,3-dimethylimidazolium acetate, 1-ethyl-3-methylimidazolium propionate, 1-propyl-3-methylimidazolium chloride, and 1-propyl-3-methylimidazolium bromide.

[0025] Although cellulose fiber raw materials can be defibrated using only ionic liquids, when there is a risk that the cellulose nanofibers may be dissolved due to the ionic liquid having too high a dissolving power for cellulose, it is preferable to add water and / or an organic solvent to the ionic liquid. The type of organic solvent to be added may be appropriately selected taking into consideration the compatibility with the ionic liquid, the affinity with cellulose, the solubility of the mixed solvent in the cellulose fiber raw materials, the viscosity, etc., and is preferably one or more selected from the group consisting of N,N-dimethylacetamide, N,N-dimethylformamide, 1-methyl-2-pyrrolidone, dimethylsulfoxide, acetonitrile, methanol, and ethanol.

[0026] The total amount of water and / or other medium used in the micronization treatment is not particularly limited as long as it is an effective amount capable of dispersing the cellulose fiber raw material, but is preferably at least 1 time by mass, more preferably at least 10 times by mass, even more preferably at least 50 times by mass, and is preferably not more than 10,000 times by mass, more preferably not more than 5,000 times by mass, even more preferably not more than 2,000 times by mass, and particularly preferably not more than 1,000 times by mass, relative to the cellulose fiber raw material.

[0027] Since the cellulose fiber raw material contains alkali soluble matter and sulfuric acid insoluble matter (lignin, etc.), the alkali soluble matter and sulfuric acid insoluble matter may be reduced by a purification process such as delignification by cooking and a bleaching process. On the other hand, the purification process such as delignification by cooking and the bleaching process cut the molecular chains of cellulose, changing the weight average molecular weight and number average molecular weight, so it is desirable to control the purification process and bleaching process of the cellulose fiber raw material so that the weight average molecular weight of the cellulose nanofiber and the ratio of the weight average molecular weight to the number average molecular weight are within an appropriate range.

[0028] In addition, there is a concern that the molecular weight of cellulose nanofibers will be reduced by the refining process such as delignification by cooking and the bleaching process, and that the cellulose fiber raw material will be altered to increase the proportion of alkali-soluble matter. Since alkali-soluble matter has poor heat resistance, it is desirable to control the refining process and bleaching process of the cellulose fiber raw material so that the amount of alkali-soluble matter contained in the cellulose fiber raw material is within a certain range or less.

[0029] In one embodiment, the cellulose fiber raw material may be chemically modified, and inorganic esters such as nitrate esters, sulfate esters, phosphate esters, silicate esters, and borates, organic esters such as acetylation and propionylation, ethers such as methyl ether, hydroxyethyl ether, hydroxypropyl ether, hydroxybutyl ether, carboxymethyl ether, and cyanoethyl ether, and TEMPO oxides obtained by oxidizing the primary hydroxyl groups of cellulose can be used as the cellulose fiber raw material.

[0030] [Number average fiber diameter and L / D ratio] In one aspect, the number average fiber diameter of the cellulose nanofibers is preferably 2 to 1000 nm from the viewpoint of obtaining a good effect of improving physical properties by the cellulose nanofibers. The number average fiber diameter of the cellulose nanofibers is more preferably 4 nm or more, or 5 nm or more, or 10 nm or more, or 15 nm or more, or 20 nm or more, and more preferably 900 nm or less, or 800 nm or less, or 700 nm or less, or 600 nm or less, or 500 nm or less, or 400 nm or less, or 300 nm or less, or 200 nm or less.

[0031] From the viewpoint of satisfactorily improving the mechanical properties of a resin composition containing cellulose nanofibers with a small amount of cellulose nanofibers, the number average fiber length (L) / number average fiber diameter (D) ratio of the cellulose nanofibers is preferably 30 or more, or 50 or more, or 80 or more, or 100 or more, or 120 or more, or 150 or more. There are no particular upper limits, but from the viewpoint of handleability, it is preferably 5,000 or less, or 3,000 or less, or 2,000 or less, or 1,000 or less.

[0032] In one embodiment, the number average fiber diameter (D), number average fiber length (L), and L / D ratio of the cellulose nanofibers of the present disclosure are values ​​measured using a scanning electron microscope (SEM) according to the following procedure. The aqueous dispersion of cellulose fibers is replaced with tert-butanol, diluted to 0.001 to 0.1% by mass, and dispersed using a high-shear homogenizer (e.g., IKA, product name "Ultra Turrax T18") under processing conditions: rotation speed 15,000 rpm x 3 minutes. The sample is cast on an osmium-deposited silicon substrate and air-dried to obtain a measurement sample, which is measured using a high-resolution scanning electron microscope (SEM). Specifically, the length (L) and diameter (D) of 100 randomly selected fibrous substances are measured in an observation field where the magnification is adjusted so that at least 100 fibrous substances are observed, and the ratio (L / D) is calculated. The number average value of the length (L), the number average value of the diameter (D), and the number average value of the ratio (L / D) are calculated for the cellulose fibers.

[0033] [BET specific surface area] In one embodiment, the BET specific surface area of ​​the cellulose nanofiber is preferably 1 m from the viewpoint of improving the dispersibility of the cellulose nanofiber in the resin composition. 2 / g or more, or 3m 2 / g or more, or 5m 2 / g or more, or 8m 2 / g or more, or 10m 2 / g or more, or 12m 2 / g or more, and from the viewpoint of ease of production of the dried product, it is preferably 50m 2 / g or less, or 40m 2 / g or less, or 30m 2 / g or less, or 25m 2 / g or less, or 20m 2 The specific surface area is determined by drying approximately 0.2 g of cellulose nanofiber at 120°C for 5 hours under vacuum using a specific surface area / pore distribution measuring device (e.g., Nova-4200e, manufactured by Quantachrome Instruments), measuring the amount of nitrogen gas adsorbed at the boiling point of liquid nitrogen at 5 points in the range of relative vapor pressure (P / P0) between 0.05 and 0.2 (multipoint method), and then calculating the BET specific surface area (m 2 / g)

[0034] [Crystallization degree] The crystallinity of the cellulose nanofibers is preferably 55% or more. When the crystallinity is in this range, the mechanical properties (strength, dimensional stability) of the cellulose itself are high, so that when the cellulose nanofibers are dispersed in a resin, the strength and dimensional stability of the resin composition tend to be high. A more preferable lower limit of the crystallinity is 60%, even more preferably 70%, and most preferably 80%. There is no particular upper limit for the crystallinity of the cellulose nanofibers, and the higher the better, but from the viewpoint of production, a preferable upper limit is 99%.

[0035] The degree of crystallinity here, when the cellulose is cellulose type I crystal (derived from natural cellulose), is calculated from the diffraction pattern (2θ / deg. is 10 to 30) obtained by measuring a sample by wide-angle X-ray diffraction using the Segal method, according to the following formula: Crystallinity (%)=[I (200) -I (amorphous) ] / I (200) ×100 I (200) : Diffraction peak intensity due to 200 plane (2θ=22.5°) in cellulose I crystal I (amorphous) : The halo peak intensity due to the amorphous phase in cellulose I crystals, which is the peak intensity at an angle 4.5° lower than the diffraction angle of the 200 plane (2θ=18.0°)

[0036] When the cellulose is cellulose II type crystal (derived from regenerated cellulose), the degree of crystallinity can be calculated from the absolute peak intensity h0 at 2θ=12.6° assigned to the (110) plane peak of cellulose II type crystal in wide-angle X-ray diffraction and the peak intensity h1 from the baseline at this interplanar spacing, according to the following formula: Crystallinity (%) =h1 / h0 ×100

[0037] [Crystal polymorphism] Known crystalline polymorphs of cellulose include types I, II, III, and IV, of which types I and II are particularly widely used, and types III and IV have been obtained on a laboratory scale but are not widely used on an industrial scale. The cellulose nanofibers of the present disclosure are preferably cellulose nanofibers containing cellulose type I crystals or cellulose type II crystals, since they have relatively high structural mobility and, by dispersing the cellulose nanofibers in a resin, a resin composition can be obtained that has a lower linear expansion coefficient and is superior in strength and elongation during tensile and bending deformation, and more preferably cellulose nanofibers containing cellulose type I crystals and having a crystallinity of 55% or more.

[0038] [Degree of polymerization] In addition, the degree of polymerization of the cellulose nanofiber is preferably 100 or more, more preferably 150 or more, more preferably 200 or more, more preferably 300 or more, more preferably 400 or more, more preferably 450 or more, and preferably 3500 or less, more preferably 3300 or less, more preferably 3200 or less, more preferably 3100 or less, and more preferably 3000 or less.

[0039] From the viewpoint of processability and mechanical property expression, it is desirable that the degree of polymerization of the cellulose nanofiber is within the above-mentioned range. From the viewpoint of processability, it is preferable that the degree of polymerization is not too high, and from the viewpoint of mechanical property expression, it is desirable that the degree of polymerization is not too low.

[0040] The degree of polymerization of cellulose nanofibers refers to the average degree of polymerization measured according to the reduced specific viscosity method using a copper ethylenediamine solution described in the Verification Test (3) of the "15th Revised Japanese Pharmacopoeia Commentary (published by Hirokawa Shoten)." Incidentally, the degree of polymerization of chemically modified cellulose nanofibers may not be calculated accurately due to the presence of chemically modifying groups. In such cases, the degree of polymerization of the cellulose nanofiber immediately before chemical modification, which is the raw material for the chemically modified cellulose nanofiber, or the raw cellulose fiber immediately before chemical modification, may be regarded as the degree of polymerization of the chemically modified cellulose nanofiber.

[0041] [Mw, Mn, Mw / Mn] In one embodiment, the weight average molecular weight (Mw) of the cellulose nanofiber is 100,000 or more, or 200,000 or more. In one embodiment, the ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight (Mn) is 6 or less, or 5.4 or less. The larger the weight average molecular weight, the fewer the number of terminal groups of the cellulose molecule. In addition, since the ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight represents the width of the molecular weight distribution, the smaller the Mw / Mn, the fewer the number of terminals of the cellulose molecule. Since the terminals of the cellulose molecules are the starting points of thermal decomposition, cellulose nanofibers with particularly high heat resistance can be obtained when the cellulose molecules of the cellulose nanofibers not only have a large weight average molecular weight but also have a narrow molecular weight distribution width at the same time. The weight average molecular weight (Mw) of the cellulose nanofiber may be, for example, 600,000 or less, or 500,000 or less, from the viewpoint of the availability of cellulose fiber raw materials. From the viewpoint of ease of production of cellulose nanofibers, the ratio (Mw / Mn) of weight average molecular weight to number average molecular weight (Mn) may be, for example, 1.5 or more, or 2 or more. Mw can be controlled to the above range by selecting a cellulose fiber raw material having an Mw appropriate for the purpose, by appropriately performing physical treatment and / or chemical treatment on the cellulose fiber raw material within an appropriate range, etc. Mw / Mn can also be controlled to the above range by selecting a cellulose fiber raw material having an Mw / Mn appropriate for the purpose, by appropriately performing physical treatment and / or chemical treatment on the cellulose fiber raw material within an appropriate range, etc. Each of the Mw and Mw / Mn of the cellulose fiber raw material may be within the above range in one embodiment. In both the control of Mw and the control of Mw / Mn, examples of the physical treatment include physical treatments that apply mechanical forces such as dry or wet grinding using a microfluidizer, ball mill, disk mill, etc., and impact, shear, friction, etc. using a crusher, homomixer, high-pressure homogenizer, ultrasonic device, etc., and examples of the chemical treatments include digestion, bleaching, acid treatment, enzyme treatment, regenerated cellulose, etc. It should be noted that the Mw, Mn, and Mw / Mn of chemically modified cellulose nanofibers may not be calculated accurately due to the presence of chemically modifying groups. In this case, the Mw, Mn, and Mw / Mn of the cellulose nanofiber immediately before chemical modification, which is the raw material for the chemically modified cellulose nanofiber, or the cellulose fiber raw material immediately before chemical modification, may be regarded as the Mw, Mn, and Mw / Mn of the chemically modified cellulose nanofiber.

[0042] The weight average molecular weight and number average molecular weight of the cellulose nanofiber referred to here are values ​​obtained by dissolving the cellulose nanofiber in N,N-dimethylacetamide containing added lithium chloride and then performing gel permeation chromatography using N,N-dimethylacetamide as a solvent.

[0043] [Control of polymerization degree and molecular weight] Methods for controlling the degree of polymerization (i.e., average degree of polymerization) or molecular weight of cellulose nanofibers include hydrolysis. Hydrolysis promotes depolymerization of amorphous cellulose inside the cellulose nanofibers, decreasing the average degree of polymerization. At the same time, hydrolysis removes impurities such as hemicellulose and lignin in addition to the above-mentioned amorphous cellulose, making the inside of the fiber more porous.

[0044] The hydrolysis method is not particularly limited, and examples thereof include acid hydrolysis, alkali hydrolysis, hydrothermal decomposition, steam explosion, and microwave decomposition. These methods may be used alone or in combination of two or more. In the acid hydrolysis method, for example, α-cellulose obtained as pulp from a fibrous plant is used as a cellulose fiber raw material, and this is dispersed in an aqueous medium, and an appropriate amount of protonic acid, carboxylic acid, Lewis acid, heteropolyacid, etc. is added, and the mixture is heated while stirring, so that the average degree of polymerization can be easily controlled. The reaction conditions such as temperature, pressure, and time at this time vary depending on the cellulose type, cellulose concentration, acid type, acid concentration, etc., but are appropriately adjusted so that the desired average degree of polymerization is achieved. For example, a condition in which a mineral acid aqueous solution of 2% by mass or less is used and cellulose nanofibers are treated at 100°C or higher under pressure for 10 minutes or more can be mentioned. Under these conditions, the catalyst component such as acid penetrates into the inside of the cellulose nanofiber, promoting hydrolysis, reducing the amount of catalyst component used, and making subsequent purification easier. The dispersion of the cellulose fiber raw material during hydrolysis may contain, in addition to water, a small amount of an organic solvent within a range that does not impair the effects of the present invention.

[0045] [Alkali-soluble polysaccharides and acid-insoluble components] Alkali-soluble polysaccharides such as hemicellulose and acid-insoluble components such as lignin exist between the microfibrils and between the microfibril bundles of cellulose nanofibers. Hemicellulose is a polysaccharide composed of sugars such as mannan and xylan, and plays a role in connecting the microfibrils by hydrogen bonding with cellulose. Lignin is a compound with an aromatic ring, and is known to be covalently bonded to hemicellulose in the cell walls of plants.

[0046] Alkali-soluble polysaccharides that may be contained in cellulose nanofibers include hemicellulose, β-cellulose, and γ-cellulose. Alkali-soluble polysaccharides are understood by those skilled in the art as components obtained as the alkali-soluble portion of holocellulose obtained by solvent extraction and chlorine treatment of plants (e.g., wood) (i.e., components obtained by removing α-cellulose from holocellulose). Alkali-soluble polysaccharides are polysaccharides containing hydroxyl groups and have poor heat resistance, and may cause inconveniences such as decomposition when exposed to heat, yellowing during thermal aging, and a decrease in strength of cellulose nanofibers. Therefore, it is preferable that the content of alkali-soluble polysaccharides in cellulose nanofibers is low.

[0047] In one aspect, the average content of alkali-soluble polysaccharides in the cellulose nanofibers is preferably 20% by mass or less, 18% by mass or less, 15% by mass or less, or 12% by mass or less, relative to 100% by mass of the cellulose nanofibers, from the viewpoint of maintaining the mechanical strength of the cellulose nanofibers during melt-kneading and suppressing yellowing. From the viewpoint of ease of production of the cellulose nanofibers, the above content may be 0.1% by mass or more, 0.5% by mass or more, 1% by mass or more, 2% by mass or more, or 3% by mass or more.

[0048] The average alkali-soluble polysaccharide content can be determined by the method described in the non-patent literature (Wood Science Experiment Manual, edited by the Japan Wood Research Society, pages 92-97, 2000), by subtracting the α-cellulose content from the holocellulose content (Wise method). This method is understood in the industry as a method for measuring the amount of hemicellulose. The alkali-soluble polysaccharide content is calculated three times for each sample, and the number average of the calculated alkali-soluble polysaccharide contents is taken as the average alkali-soluble polysaccharide content. The alkali-soluble polysaccharide content of chemically modified cellulose nanofibers may not be calculated accurately due to the presence of chemical modification groups. In this case, the average alkali-soluble polysaccharide content of the cellulose nanofibers immediately before chemical modification, which are the raw material for chemically modified cellulose nanofibers, or the cellulose fiber raw material immediately before chemical modification, may be regarded as the average alkali-soluble polysaccharide content of the chemically modified cellulose nanofibers.

[0049] Those skilled in the art will understand that acid-insoluble components that cellulose nanofibers may contain are insoluble components that remain after a defatted sample obtained by solvent extraction of a plant (e.g., wood) is treated with sulfuric acid. Specifically, the acid-insoluble component is lignin derived from aromatic compounds, but is not limited thereto. Since the acid-insoluble component is often colored by itself and may cause inconveniences such as impairing the appearance of the resin composition and causing yellowing during thermal aging, it is preferable that the average content of acid-insoluble components in the cellulose nanofibers is low.

[0050] In one aspect, the average content of acid-insoluble components in the cellulose nanofibers is preferably 10% by mass or less, 5% by mass or less, or 3% by mass or less, relative to 100% by mass of the cellulose nanofibers, from the viewpoint of avoiding a decrease in heat resistance of the cellulose nanofibers and the associated discoloration. From the viewpoint of ease of production of the cellulose nanofibers, the above content may be 0.1% by mass or more, 0.2% by mass or more, or 0.3% by mass or more.

[0051] The average acid-insoluble content is determined as a quantity of acid-insoluble components using the Clason method described in the non-patent literature (Wood Science Experiment Manual, edited by the Japan Wood Research Society, pages 92-97, 2000). This method is understood in the industry as a method for measuring the amount of lignin. The sample is stirred in a sulfuric acid solution to dissolve cellulose, hemicellulose, etc., and then filtered through glass fiber filter paper, and the resulting residue corresponds to the acid-insoluble components. The acid-insoluble component content is calculated from the weight of the acid-insoluble components, and the number average of the acid-insoluble component contents calculated for the three samples is taken as the average acid-insoluble component content. The average acid-insoluble component content of chemically modified cellulose nanofibers may not be calculated accurately due to the presence of chemical modification groups. In this case, the average alkali-soluble polysaccharide content of the cellulose nanofibers immediately before chemical modification, which are the raw material for chemically modified cellulose nanofibers, or the cellulose fiber raw material immediately before chemical modification, may be considered as the average alkali-soluble polysaccharide content of the chemically modified cellulose nanofibers.

[0052] [Thermal decomposition onset temperature (T D )] The thermal decomposition temperature of cellulose nanofiber (T D ) is, in one aspect, preferably 250° C. or higher, or 260° C. or higher, or 270° C. or higher, or 275° C. or higher, or 280° C. or higher, or 285° C. or higher, from the viewpoint of avoiding thermal degradation during melt-kneading and being able to exert mechanical strength. The higher the thermal decomposition onset temperature, the more preferable it is, but from the viewpoint of ease of production of cellulose nanofibers, it may be, for example, 320° C. or lower, 310° C. or lower, or 300° C. or lower.

[0053] [Temperature at 1% weight loss (T 1% ), 250℃ weight loss rate (T 250℃ )] The temperature at which the cellulose nanofiber loses 1 wt% weight (T 1% From the viewpoint of avoiding thermal deterioration during melt-kneading and exhibiting mechanical strength, in one aspect, the temperature is preferably 260° C. or higher, 270° C. or higher, 275° C. or higher, 280° C. or higher, 285° C. or higher, or 290° C. or higher.1% The higher the temperature, the more preferable; however, from the viewpoint of ease of production of cellulose nanofibers, the temperature may be, for example, 330° C. or less, 320° C. or less, or 310° C. or less.

[0054] Weight loss rate of cellulose nanofiber at 250°C (T 250℃ From the viewpoint of avoiding thermal deterioration during melt-kneading and exhibiting mechanical strength, in one aspect, T is preferably 15% or less, or 12% or less, or 10% or less, or 8% or less, or 6% or less, or 5% or less, or 4% or less, or 3% or less. 250℃ The lower the better, but from the viewpoint of ease of production of cellulose nanofibers, it may be, for example, 0.1% or more, or 0.5% or more, or 0.7% or more, or 1.0% or more.

[0055] In this disclosure, the T of cellulose nanofibers D is a value obtained from a graph in which the horizontal axis is temperature and the vertical axis is the weight residual rate % in a thermal decomposition onset temperature analysis under nitrogen flow. Cellulose nanofiber is heated from room temperature to 150°C at a heating rate of 10°C / min in a nitrogen flow of 100 ml / min, and then held at 150°C for 1 hour, after which it is heated to 450°C at a heating rate of 10°C / min. Starting from the weight at 150°C (a state where most moisture has been removed) (weight loss of 0 wt%), the temperature at which 1 wt% weight loss (T 1% ) and the temperature at which the weight loss reaches 2 wt% (T 2% The temperature at the point where this line intersects with the horizontal line (baseline) that passes through the starting point of the weight loss of 0 wt% is called T D It is defined as:

[0056] 1% weight loss temperature (T 1% ) is the above T D This is the temperature at which the weight loss reaches 1% by weight, starting from the weight at 150°C, when the temperature is continued to be increased using the method described above.

[0057] Weight loss rate of cellulose nanofiber at 250°C (T 250℃) is the weight loss rate when cellulose nanofibers are held at 250°C under nitrogen flow for 2 hours in TG analysis. The cellulose nanofibers are heated from room temperature to 150°C at a rate of 10°C / min in a nitrogen flow of 100 ml / min, held at 150°C for 1 hour, then heated from 150°C to 250°C at a rate of 10°C / min, and held at 250°C for 2 hours. The weight W0 at the time when 250°C is reached is taken as the starting point, and the weight after holding at 250°C for 2 hours is taken as W1, and is calculated using the following formula. Weight change rate at 250℃ (%): (W1-W0) / W0×100

[0058] [Porous sheet] The properties of cellulose nanofiber (crystallinity, crystalline polymorphism, degree of polymerization, Mw, Mn, Mw / Mn, average content of alkali-soluble polysaccharides, average content of acid-insoluble components, T D , T 1% , T 250℃ The measurements of the above may vary greatly depending on the shape of the measurement sample. In order to perform stable and reproducible measurements, a distortion-free porous sheet is used as the measurement sample. The porous sheet is prepared as follows.

[0059] First, a concentrated cake of cellulose nanofibers with a solid content of 10% by mass or more is added to tert-butanol, and a dispersion process is then performed using a mixer or the like until no aggregates remain. The concentration is adjusted to 0.5% by mass for 0.5 g of cellulose nanofiber solids. 100 g of the resulting tert-butanol dispersion is filtered on filter paper. The filtered material is not peeled off from the filter paper, but is sandwiched together with the filter paper between two sheets of larger filter paper, and dried for 5 minutes in an oven at 150°C while pressing down the edges of the larger filter paper with a weight. The filter paper is then peeled off to obtain a porous sheet with little distortion. When the air resistance R of this sheet is 10 g / m2, the sheet weight is 10 g / m2. 2 A porous sheet with a permeability of 100 sec / 100 ml or less is used as the measurement sample.

[0060] The air permeability resistance R was measured by measuring the basis weight W (g / m2) of a porous sheet sample left to stand for one day in an environment of 23°C and 50% RH. 2 ), and then the air resistance R (sec / 100ml) is measured using an Oken air resistance tester (e.g., Asahi Seiko Co., Ltd., Model EG01). 2 Calculate the value per unit area. Weight 10g / m 2 Air resistance per unit (sec / 100ml) = R / W x 10

[0061] [Physical properties of cellulose nanofibers in resin composition] Various physical properties of cellulose nanofibers in the resin composition (number average fiber length, number average fiber diameter, L / D ratio, crystallinity, crystal polymorphism, polymerization degree, Mw, Mn, Mw / Mn, average content of alkali-soluble polysaccharides, average content of acid-insoluble components, T D , T 1% , T 250℃ (and DS, DSs, DS heterogeneity ratio, and coefficient of variation of DS heterogeneity ratio, etc., described below) are analyzed by the following method. The resin components in the resin composition are dissolved in an organic or inorganic solvent capable of dissolving the resin components of the resin composition, the cellulose nanofibers are separated, thoroughly washed with the solvent, and the solvent is replaced with tert-butanol. The cellulose nanofiber tert-butanol slurry is then analyzed using the same measurement method as above, and various physical properties of the cellulose nanofibers in the resin composition are calculated.

[0062] [Chemical modification] The cellulose nanofibers may be chemically modified cellulose nanofibers (also referred to as chemically modified cellulose nanofibers). The cellulose nanofibers may be chemically modified in advance, for example, at the stage of raw cellulose fiber material, during or after defibration treatment, or may be chemically modified during or after preparation of a slurry as a dispersion, or during or after the drying and granulation process.

[0063] As a modification agent for cellulose nanofibers, a compound that reacts with the hydroxyl groups of cellulose can be used, such as an esterification agent, an etherification agent, and a silylating agent. In a preferred embodiment, the chemical modification is acylation using an esterification agent, and particularly preferably acetylation. As the esterification agent, acid halides, acid anhydrides, vinyl carboxylates, and carboxylic acids are preferred.

[0064] The acid halide may be at least one selected from the group consisting of compounds represented by the following formula: R 1 -C(=O)-X (In the formula, R 1 represents an alkyl group having 1 to 24 carbon atoms, an alkenyl group having 2 to 24 carbon atoms, a cycloalkyl group having 3 to 24 carbon atoms, or an aryl group having 6 to 24 carbon atoms, and X is Cl, Br, or I. Specific examples of acid halides include, but are not limited to, acetyl chloride, acetyl bromide, acetyl iodide, propionyl chloride, propionyl bromide, propionyl iodide, butyryl chloride, butyryl bromide, butyryl iodide, benzoyl chloride, benzoyl bromide, and benzoyl iodide. Among them, acid chlorides can be preferably used in terms of reactivity and handling. In addition, in the reaction of acid halides, one or more alkaline compounds may be added to act as a catalyst and neutralize the by-product acidic substances. Specific examples of alkaline compounds include, but are not limited to, tertiary amine compounds such as triethylamine and trimethylamine; and nitrogen-containing aromatic compounds such as pyridine and dimethylaminopyridine.

[0065] As the acid anhydride, any suitable acid anhydride can be used. For example, Saturated aliphatic monocarboxylic acid anhydrides, such as acetic acid, propionic acid, (iso)butyric acid, and valeric acid; unsaturated aliphatic monocarboxylic acid anhydrides, such as (meth)acrylic acid and oleic acid; Alicyclic monocarboxylic acid anhydrides such as cyclohexanecarboxylic acid and tetrahydrobenzoic acid; Aromatic monocarboxylic acid anhydrides such as benzoic acid and 4-methylbenzoic acid; Examples of dibasic carboxylic acid anhydrides include saturated aliphatic dicarboxylic acid anhydrides such as succinic anhydride and adipic acid, unsaturated aliphatic dicarboxylic acid anhydrides such as maleic anhydride and itaconic anhydride, alicyclic dicarboxylic acid anhydrides such as 1-cyclohexene-1,2-dicarboxylic acid anhydride, hexahydrophthalic anhydride and methyltetrahydrophthalic anhydride, and aromatic dicarboxylic acid anhydrides such as phthalic anhydride and naphthalic anhydride; Examples of polybasic carboxylic acid anhydrides having three or more bases include polycarboxylic acids (anhydrides) such as trimellitic anhydride and pyromellitic anhydride. In addition, in the reaction of an acid anhydride, one or more types of acidic compounds such as sulfuric acid, hydrochloric acid, phosphoric acid, etc., or Lewis acids (for example, Lewis acid compounds represented by MYn, where M represents a semimetal element such as B, As, Ge, etc., or a base metal element such as Al, Bi, In, etc., or a transition metal element such as Ti, Zn, Cu, etc., or a lanthanoid element, n is an integer corresponding to the atomic valence of M and represents 2 or 3, and Y represents a halogen atom, OAc, OCOCF3, ClO4, SbF6, PF6, or OSO2CF3(OTf)), or alkaline compounds such as triethylamine, pyridine, etc. may be added as a catalyst.

[0066] The vinyl carboxylate may be represented by the following formula: R-COO-CH=CH2 {wherein R is any one of an alkyl group having 1 to 24 carbon atoms, an alkenyl group having 2 to 24 carbon atoms, a cycloalkyl group having 3 to 16 carbon atoms, and an aryl group having 6 to 24 carbon atoms.} is preferred. The vinyl carboxylate is more preferably at least one selected from the group consisting of vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl cyclohexanecarboxylate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate, vinyl octylate, divinyl adipate, vinyl methacrylate, vinyl crotonate, vinyl octylate, vinyl benzoate, and vinyl cinnamate. In the esterification reaction with a vinyl carboxylate, one or more catalysts selected from the group consisting of alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal carbonates, alkaline earth metal carbonates, alkali metal hydrogencarbonates, primary to tertiary amines, quaternary ammonium salts, imidazole and derivatives thereof, pyridine and derivatives thereof, and alkoxides may be added.

[0067] Examples of the alkali metal hydroxides and alkaline earth metal hydroxides include sodium hydroxide, potassium hydroxide, lithium hydroxide, calcium hydroxide, barium hydroxide, etc. Examples of the alkali metal carbonates, alkaline earth metal carbonates, and alkali metal hydrogen carbonates include lithium carbonate, sodium carbonate, potassium carbonate, cesium carbonate, magnesium carbonate, calcium carbonate, barium carbonate, lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, cesium hydrogen carbonate, etc.

[0068] The primary, secondary and tertiary amines refer to primary, secondary and tertiary amines, and specific examples thereof include ethylenediamine, diethylamine, proline, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethyl-1,3-propanediamine, N,N,N',N'-tetramethyl-1,6-hexanediamine, tris(3-dimethylaminopropyl)amine, N,N-dimethylcyclohexylamine and triethylamine.

[0069] Examples of imidazole and its derivatives include 1-methylimidazole, 3-aminopropylimidazole, and carbonyldiimidazole.

[0070] Examples of pyridine and its derivatives include N,N-dimethyl-4-aminopyridine and picoline.

[0071] Examples of the alkoxide include sodium methoxide, sodium ethoxide, and potassium t-butoxide.

[0072] The carboxylic acid may be at least one selected from the group consisting of compounds represented by the following formulas: R-COOH (In the formula, R represents an alkyl group having 1 to 16 carbon atoms, an alkenyl group having 2 to 16 carbon atoms, a cycloalkyl group having 3 to 16 carbon atoms, or an aryl group having 6 to 16 carbon atoms.)

[0073] Specific examples of carboxylic acids include at least one selected from the group consisting of acetic acid, propionic acid, butyric acid, caproic acid, cyclohexane carboxylic acid, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, pivalic acid, methacrylic acid, crotonic acid, octylic acid, benzoic acid, and cinnamic acid.

[0074] Among these carboxylic acids, at least one selected from the group consisting of acetic acid, propionic acid, and butyric acid, and particularly acetic acid, is preferred from the viewpoint of reaction efficiency. In addition, in the reaction of carboxylic acid, one or more types of acidic compounds such as sulfuric acid, hydrochloric acid, phosphoric acid, etc., or Lewis acids (for example, Lewis acid compounds represented by MYn, where M represents a semimetal element such as B, As, Ge, etc., or a base metal element such as Al, Bi, In, etc., or a transition metal element such as Ti, Zn, Cu, etc., or a lanthanoid element, n is an integer corresponding to the atomic valence of M and represents 2 or 3, and Y represents a halogen atom, OAc, OCOCF3, ClO4, SbF6, PF6, or OSO2CF3(OTf)), or alkaline compounds such as triethylamine, pyridine, etc. may be added as a catalyst.

[0075] Among these esterification reactants, at least one selected from the group consisting of acetic anhydride, propionic anhydride, butyric anhydride, vinyl acetate, vinyl propionate, vinyl butyrate, and acetic acid, and among these, acetic anhydride and vinyl acetate are preferred from the viewpoint of reaction efficiency.

[0076] [Acyl Substitution Degree (DS)] When cellulose nanofibers are chemically modified (for example, by hydrophobization such as acylation), the dispersibility of the cellulose nanofibers in the resin tends to be good, but the cellulose nanofibers of the present disclosure can exhibit good dispersibility in the resin even when unsubstituted or with a low degree of substitution by combining with a low Tg polyphenylene ether. When the cellulose nanofibers are esterified cellulose nanofibers, the degree of acyl substitution (DS) is preferably 0.1 or more, or 0.2 or more, or 0.25 or more, or 0.3 or more, or 0.5 or more in terms of obtaining esterified cellulose nanofibers with a high thermal decomposition onset temperature, and is preferably 2.0 or less, or 1.8 or less, or 1.5 or less, or 1.2 or less, or 1.0 or less, or 0.8 or less, or 0.7 or less, or 0.6 or less, or 0.5 or less in terms of obtaining esterified cellulose nanofibers with a high thermal decomposition onset temperature because an unmodified cellulose skeleton remains in the esterified cellulose nanofibers.

[0077] When the modification group of the chemically modified cellulose nanofiber is an acyl group, the degree of acyl substitution (DS) can be calculated from the peak intensity ratio of the peak derived from the acyl group to the peak derived from the cellulose skeleton from the reflection infrared absorption spectrum of the esterified cellulose nanofiber. The peak of the absorption band of C=O based on the acyl group is at 1730 cm -1 The absorption band of CO based on the cellulose backbone appears at 1030 cm -1 The DS of esterified cellulose nanofibers was calculated by plotting a correlation graph between the DS obtained from solid-state NMR measurements of esterified cellulose nanofibers (described below) and the modification ratio (IR index 1030), which is defined as the ratio of the peak intensity of the absorption band of C=O based on acyl groups to the peak intensity of the absorption band of CO in the cellulose backbone chain, and then calculating the calibration curve from the correlation graph. Degree of substitution DS = 4.13 × IR index (1030) It can be found by using

[0078] The method for calculating the DS of esterified cellulose nanofibers using solid-state NMR is as follows: 13 C solid-state NMR measurement was performed, and the intensity can be calculated using the area intensity (Inf) of a signal assigned to one carbon atom derived from the modifying group relative to the total area intensity (Inp) of signals assigned to carbons C1-C6 derived from the pyranose ring of cellulose, which appear in the range from 50 ppm to 110 ppm, using the following formula. DS = (Inf) x 6 / (Inp) For example, when the modifying group is an acetyl group, the signal at 23 ppm assigned to -CH3 may be used. Use 13 The conditions for the C solid-state NMR measurement are, for example, as follows: Equipment:Bruker Biospin Avance500WB Frequency: 125.77MHz Measurement method: DD / MAS method Waiting time: 75sec NMR sample tube: 4mmφ Accumulation times: 640 times (approx. 14 hours) MAS: 14,500Hz Chemical shift reference: glycine (external reference: 176.03 ppm)

[0079] The DS heterogeneity ratio (DSs / DSt), defined as the ratio of the degree of modification (DSs) of the fiber surface to the degree of modification (DSt) of the entire fiber of the chemically modified cellulose nanofiber (which is synonymous with the above-mentioned degree of acyl substitution (DS)), is preferably 1.05 or more. The larger the value of the DS heterogeneity ratio, the more pronounced the sheath-core-like heterogeneous structure (i.e., a structure in which the fiber surface is highly chemically modified while the fiber center retains a cellulose structure close to the original unmodified structure), and while maintaining high tensile strength and dimensional stability derived from cellulose, it is possible to improve the affinity with the resin when composited with the resin and to improve the dimensional stability of the resin composition. The DS heterogeneity ratio is more preferably 1.1 or more, or 1.2 or more, or 1.3 or more, or 1.5 or more, or 2 or more, and from the viewpoint of ease of production of the chemically modified cellulose nanofiber, it is preferably 30 or less, or 20 or less, or 10 or less, or 6 or less, or 4 or less, or 3 or less. The value of DSs varies depending on the degree of modification of the esterified cellulose nanofiber, but as an example, it is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.3 or more, even more preferably 0.5 or more, and preferably 3.0 or less, more preferably 2.5 or less, particularly preferably 2.0 or less, even more preferably 1.5 or less, particularly preferably 1.2 or less, and most preferably 1.0 or less. The preferred range of DSt is as described above for the acyl substituent (DS).

[0080] The smaller the coefficient of variation (CV) of the DS heterogeneity ratio of the chemically modified cellulose nanofiber, the smaller the variation in various physical properties of the resin composition, and therefore the more preferable. The coefficient of variation is preferably 50% or less, or 40% or less, or 30% or less, or 20% or less. The coefficient of variation can be further reduced, for example, by a method in which a cellulose fiber raw material is defibrated and then chemically modified to obtain a chemically modified cellulose nanofiber (i.e., a sequential method), whereas it can be increased by a method in which defibration and chemical modification of the cellulose fiber raw material are performed simultaneously (i.e., a simultaneous method). Although the mechanism of this action is not clear, in the simultaneous method, chemical modification is more likely to proceed in the thin fibers generated in the early stage of defibration, and when hydrogen bonds between cellulose microfibrils are reduced by chemical modification, defibration proceeds further, which is thought to result in an increase in the coefficient of variation of the DS heterogeneity ratio.

[0081] The coefficient of variation (CV) of the DS heterogeneity ratio is calculated by taking 100 g of an aqueous dispersion of chemically modified cellulose nanofiber (solid content of 10 mass% or more) and freeze-pulverizing 10 g portions to use as measurement samples. The DS heterogeneity ratio is calculated from the DSt and DSs of the 10 samples, and then the standard deviation (σ) and arithmetic mean (μ) of the DS heterogeneity ratio among the obtained 10 samples are used to calculate the coefficient of variation (CV) of the DS heterogeneity ratio using the following formula. DS heterogeneity ratio = DSs / DSt Coefficient of variation (%) = standard deviation σ / arithmetic mean μ × 100

[0082] The DSs is calculated as follows. That is, the esterified cellulose nanofibers powdered by freeze-pulverization are placed on a dish-shaped sample stage with a diameter of 2.5 mm, the surface is pressed down to make it flat, and then measurement is performed by X-ray photoelectron spectroscopy (XPS). The XPS spectrum reflects the constituent elements and chemical bond state of only the surface layer of the sample (typically about a few nm). Peak separation is performed on the obtained C1s spectrum, and the DSs can be calculated by the following formula based on the area intensity (Ixf) of the peak assigned to one carbon atom derived from the modifying group relative to the area intensity (Ixp) of the peak (289 eV, CC bond) assigned to carbons C2-C6 derived from the pyranose ring of cellulose. DSs = (Ixf) x 5 / (Ixp) For example, if the modifying group is an acetyl group, after peak separation of the C1s spectrum at 285 eV, 286 eV, 288 eV, and 289 eV, the peak at 289 eV can be used for Ixp and the peak derived from the O-C=O bond of the acetyl group (286 eV) can be used for Ixf. The conditions for the XPS measurement are as follows, for example: Equipment used: ULVAC-Phi VersaProbe II Excitation source: mono.AlKα 15kV×3.33mA Analysis size: Approx. 200 μm φ Photoelectron extraction angle: 45° Capture Area Narrow scan: C 1s, O 1s Pass Energy: 23.5eV

[0083] <Thermoplastic resin> The thermoplastic resin contained in the resin composition of the present disclosure may be, for example, a crystalline resin having a melting point in the range of 100°C to 350°C, an amorphous resin having a glass transition temperature in the range of 100°C to 250°C, etc. In the present disclosure, the melting point refers to the peak top temperature of the endothermic peak that appears when the temperature is increased from 23°C at a heating rate of 10°C / min using a differential scanning calorimeter (DSC), and when two or more endothermic peaks appear, it refers to the peak top temperature of the endothermic peak on the highest temperature side. The enthalpy of the endothermic peak at this time is preferably 10 J / g or more, more preferably 20 J / g or more. In addition, when measuring, it is preferable to use a sample that is once heated to a temperature condition of melting point + 20°C or more to melt the resin, and then cooled to 23°C at a temperature decreasing rate of 10°C / min. In the present disclosure, the glass transition temperature of a resin refers to the peak top temperature at which the storage modulus is greatly reduced and the loss modulus is maximized when measured using a dynamic viscoelasticity measuring device at a heating rate of 2°C / min from 23°C and an applied frequency of 10Hz. When two or more peaks of the loss modulus appear, it refers to the peak top temperature of the peak on the highest temperature side. In this case, the measurement frequency is preferably at least once every 30 seconds to improve the measurement accuracy. In addition, there is no particular restriction on the method of preparing the measurement sample, but from the viewpoint of eliminating the influence of molding distortion, it is preferable to use a cut piece of a heat press molded product, and it is preferable from the viewpoint of heat conduction that the size (width and thickness) of the cut piece is as small as possible.

[0084] Examples of the thermoplastic resin include polyolefin resin, polyamide resin, polyester resin, polyacetal resin, polyphenylene ether resin (in one embodiment, different from the low Tg polyphenylene ether of the present disclosure), polyphenylene sulfide resin, polycarbonate resin, acrylic resin, and a mixture of two or more of these, and may include or be an elastomer resin. From the viewpoint of handling and cost, preferred are polyolefin resin, polyamide resin, polyester resin, polyacetal resin, etc., more preferred are polyamide resin, polyolefin resin, and polyacetal resin, and particularly preferred are polyamide resin and polyacetal resin. From the viewpoint of enhancing the heat resistance of the resin composition, the melting point of the thermoplastic resin (particularly the crystalline resin) is preferably 140°C or more, or 150°C or more, or 160°C or more, or 170°C or more, or 180°C or more, or 190°C or more, or 200°C or more, or 210°C or more, or 220°C or more, or 230°C or more, or 240°C or more, or 245°C or more, or 250°C or more.

[0085] The melting point of the thermoplastic resin can be, for example, 150°C to 190°C or 160°C to 180°C for a resin with a relatively low melting point (such as a polyolefin-based resin), and 220°C to 350°C or 230°C to 320°C for a resin with a relatively high melting point (such as a polyamide-based resin).

[0086] In another preferred embodiment, the thermoplastic resin may be at least one selected from the group consisting of polyolefin resins, polyacetal resins, polycarbonate resins, polyamide resins, polyester resins, polyphenylene ether resins, and acrylic resins, and may include or be an elastomer resin. In a particularly preferred embodiment, the thermoplastic resin may be at least one selected from the group consisting of polyolefin resins, polyacetal resins, and polyamide resins.

[0087] The polyolefin resin preferred as the thermoplastic resin is a polymer obtained by polymerizing olefins (e.g., α-olefins) and / or alkenes as monomer units.Specific examples of the polyolefin resin include ethylene (co)polymers such as low-density polyethylene (e.g., linear low-density polyethylene), high-density polyethylene, ultra-low-density polyethylene, and ultra-high-molecular-weight polyethylene, polypropylene (co)polymers such as polypropylene, ethylene-propylene copolymer, and ethylene-propylene-diene copolymer, and copolymers of ethylene and α-olefins such as ethylene-acrylic acid copolymer, ethylene-methyl methacrylate copolymer, and ethylene-glycidyl methacrylate copolymer.

[0088] Here, the most preferred polyolefin resin is polypropylene. In particular, polypropylene having a melt mass flow rate (MFR) of 3 g / 10 min or more and 30 g / 10 min or less, measured at 230 ° C. and a load of 21.2 N according to ISO1133, is preferred. The lower limit of MFR is more preferably 5 g / 10 min, even more preferably 6 g / 10 min, and most preferably 8 g / 10 min. The upper limit is more preferably 25 g / 10 min, even more preferably 20 g / 10 min, and most preferably 18 g / 10 min. From the viewpoint of improving the toughness of the resin composition, it is desirable that MFR does not exceed the above upper limit, and from the viewpoint of the flowability of the resin composition, it is desirable that MFR does not exceed the above lower limit.

[0089] In addition, in order to increase the affinity with cellulose nanofibers, an acid-modified polyolefin resin can also be suitably used. As the acid used for the acid modification, a mono- or polycarboxylic acid can be used, and examples thereof include maleic acid, fumaric acid, succinic acid, phthalic acid and their anhydrides, and citric acid. Maleic acid or its anhydride is particularly preferred because it is easy to increase the modification rate. There is no particular restriction on the modification method, but a method in which a polyolefin resin is heated to a melting point or higher in the presence or absence of a peroxide and melt-kneaded is common. As the polyolefin resin to be acid-modified, all of the above-mentioned polyolefin resins can be used, but polypropylene is particularly suitable. The acid-modified polypropylene resin may be used alone, but it is more preferable to use it in combination with an unmodified polypropylene resin in order to adjust the modification rate of the resin as a whole. In this case, the ratio of the acid-modified polypropylene resin to all polypropylene resins is preferably 0.5% by mass to 50% by mass. A more preferred lower limit is 1 mass%, or 2 mass%, or 3 mass%, or 4 mass%, or 5 mass%. A more preferred upper limit is 45 mass%, or 40 mass%, or 35 mass%, or 30 mass%, or 20 mass%. In order to maintain the interfacial strength between the resin and the cellulose nanofiber, a content equal to or greater than the lower limit is preferred, and in order to maintain the ductility of the resin, a content equal to or less than the upper limit is preferred.

[0090] The melt mass flow rate (MFR) of the acid-modified polypropylene resin measured in accordance with ISO 1133 at 230°C under a load of 21.2 N is preferably 50 g / 10 min or more, 100 g / 10 min or more, 150 g / 10 min or more, or 200 g / 10 min or more from the viewpoint of increasing the affinity at the interface between the resin and the cellulose nanofiber. There is no particular upper limit, but it is preferably 500 g / 10 min from the viewpoint of maintaining mechanical strength.

[0091] Examples of polyamide-based resins that are preferable as the thermoplastic resin include polyamides obtained by polycondensation reaction of lactams (e.g., polyamide 6, polyamide 11, polyamide 12, etc.); diamines (e.g., 1,6-hexanediamine, 2-methyl-1,5-pentanediamine, 1,7-heptanediamine, 2-methyl-1-6-hexanediamine, 1,8-octanediamine, 2-methyl-1,7-heptanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, m-xylylenediamine, etc.) and dicarboxylic acids (e.g., butanedioic acid, pentanedioic acid, hexanedioic acid, , heptanedioic acid, octanedioic acid, nonanedioic acid, decanedioic acid, benzene-1,2-dicarboxylic acid, benzene-1,3-dicarboxylic acid, benzene-1,4-dicarboxylic acid, cyclohexane-1,3-dicarboxylic acid, cyclohexane-1,4-dicarboxylic acid, etc.) (for example, polyamide 6,6, polyamide 6,10, polyamide 6,11, polyamide 6,12, polyamide 6,T, polyamide 6,I, polyamide 9,T, polyamide 10,T, polyamide 2M5,T, polyamide MXD,6, polyamide 6,C, polyamide 2M5,C, etc.); and copolymers in which these are copolymerized (for example, polyamide 6,T / 6,I, etc.).

[0092] Among these polyamide resins, aliphatic polyamides such as polyamide 6, polyamide 11, polyamide 12, polyamide 6,6, polyamide 6,10, polyamide 6,11, and polyamide 6,12, and alicyclic polyamides such as polyamide 6,C and polyamide 2M5,C are more preferred.

[0093] From the viewpoint of improving the heat resistance of the resin composition, the melting point of the polyamide resin is preferably 220°C or more, or 230°C or more, or 240°C or more, or 245°C or more, or 250°C or more, and from the viewpoint of ease of production of the resin composition, the melting point is preferably 350°C or less, or 320°C or less, or 300°C or less.

[0094] The terminal carboxyl group concentration of the polyamide resin is not particularly limited, but is preferably 20 μmol / g or more, or 30 μmol / g or more, and preferably 150 μmol / g or less, or 100 μmol / g or less, or 80 μmol / g or less.

[0095] In the polyamide-based resin, the ratio of carboxyl end groups to all end groups ([COOH] / [total end groups]) is preferably 0.30 or more, or 0.35 or more, or 0.40 or more, or 0.45 or more from the viewpoint of dispersibility of the cellulose nanofibers in the resin composition, and is preferably 0.95 or less, or 0.90 or less, or 0.85 or less, or 0.80 or less from the viewpoint of the color tone of the resin composition.

[0096] The terminal group concentration of the polyamide resin can be adjusted by a known method, such as adding a terminal regulator (e.g., a diamine compound, a monoamine compound, a dicarboxylic acid compound, a monocarboxylic acid compound, an acid anhydride, a monoisocyanate, a monoacid halide, a monoester, a monoalcohol, etc.) that reacts with the terminal group during polymerization of the polyamide to the polymerization liquid so as to obtain a predetermined terminal group concentration.

[0097] Examples of the terminal regulator that reacts with the terminal amino group include aliphatic monocarboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, pivalic acid, and isobutyric acid; alicyclic monocarboxylic acids such as cyclohexanecarboxylic acid; aromatic monocarboxylic acids such as benzoic acid, toluic acid, α-naphthalenecarboxylic acid, β-naphthalenecarboxylic acid, methylnaphthalenecarboxylic acid, and phenylacetic acid; and mixtures of a plurality of terminal regulators selected from the above. Among these, from the viewpoints of reactivity, stability of the blocked terminal, and cost, one or more terminal regulators selected from the group consisting of acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, and benzoic acid are preferred, and acetic acid is most preferred.

[0098] Examples of the terminal regulator that reacts with the terminal carboxyl group include aliphatic monoamines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, dibutylamine, etc., alicyclic monoamines such as cyclohexylamine, dicyclohexylamine, etc., aromatic monoamines such as aniline, toluidine, diphenylamine, naphthylamine, etc., and any mixtures thereof. Among these, one or more terminal regulators selected from the group consisting of butylamine, hexylamine, octylamine, decylamine, stearylamine, cyclohexylamine, and aniline are preferred in terms of reactivity, boiling point, stability of the blocked terminal, price, etc.

[0099] The concentration of amino end groups and carboxyl end groups of the polyamide resin is 1 It can be determined from the integral value of the characteristic signal corresponding to each terminal group by H-NMR. This method is preferable in terms of accuracy and simplicity. More specifically, it is recommended to use the method described in JP-A-7-228775, use deuterated trifluoroacetic acid as the measurement solvent, and set the number of integration scans to 300 or more.

[0100] The intrinsic viscosity [η] of the polyamide resin measured under the condition of 30°C in concentrated sulfuric acid is preferably 0.6 to 2.0 dL / g, or 0.7 to 1.4 dL / g, or 0.7 to 1.2 dL / g, or 0.7 to 1.0 dL / g, from the viewpoint that the fluidity in the mold is good and the appearance of the molded piece is good when the resin composition is injection molded. In the present disclosure, the "intrinsic viscosity" is synonymous with the viscosity generally called the limiting viscosity. The intrinsic viscosity is obtained by measuring the ηsp / c of ​​several measurement solvents having different concentrations under the temperature condition of 30°C in 96% concentrated sulfuric acid, deriving the relational equation between each of the ηsp / c and the concentration (c), and extrapolating the concentration to zero. The value extrapolated to zero is the intrinsic viscosity. Details of the above method are described, for example, in Polymer Process Engineering (Prentice-Hall, Inc. 1994), pages 291 to 294, etc. From the viewpoint of accuracy, it is desirable to set at least four concentrations in the above-mentioned measurement solvents having different concentrations (for example, 0.05 g / dL, 0.1 g / dL, 0.2 g / dL, and 0.4 g / dL).

[0101] As the polyester resin preferred as the thermoplastic resin, one or more selected from polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene adipate terephthalate (PBAT), polyhydroxyalkanoic acid (PHA), polylactic acid (PLA), polyarylate (PAR), etc. can be used. Among them, PET, PBS, PBSA, PBT and PEN are more preferred, and PBS, PBSA and PBT are particularly preferred.

[0102] The terminal groups of the polyester resin can be changed as desired by the monomer ratio during polymerization, the presence or absence and amount of addition of a terminal stabilizer, etc. The ratio of carboxyl terminal groups to all terminal groups of the polyester resin ([COOH] / [total terminal groups]) is preferably 0.30 or more, or 0.35 or more, or 0.40 or more, or 0.45 or more from the viewpoint of dispersibility of cellulose nanofibers in the resin composition, and is preferably 0.95 or less, or 0.90 or less, or 0.85 or less, or 0.80 or less from the viewpoint of the color tone of the resin composition.

[0103] As the polyacetal resin preferred as the thermoplastic resin, homopolyacetal made from formaldehyde and copolyacetal containing trioxane as the main monomer and 1,3-dioxolane as the comonomer component are generally used, and although both can be used, copolyacetal is preferred from the viewpoint of thermal stability during processing. The amount of the structure derived from the comonomer component (e.g., 1,3-dioxolane) is preferably 0.01 mol% or more, or 0.05 mol% or more, or 0.1 mol% or more, or 0.2 mol% or more from the viewpoint of thermal stability during extrusion processing and molding processing, and is preferably 4.0 mol% or less, or 3.5 mol% or less, or 3.0 mol% or less, or 2.5 mol% or less, or 2.3 mol% or less from the viewpoint of mechanical strength.

[0104] In the present disclosure, in one embodiment, an elastomer is a material (specifically, a natural or synthetic polymer material) that is elastic at room temperature (23°C). In addition, being elastic in one embodiment means that the storage modulus at 23°C and 10 Hz measured by dynamic viscoelasticity measurement is 1 MPa or more and 100 MPa or less. The thermoplastic elastomer may be a conjugated diene polymer or a non-conjugated diene polymer, and in one embodiment, is a crosslinked product. Examples of elastomeric resins that are preferable as thermoplastic resins include rubbers such as natural rubber, styrene-butadiene rubber, butadiene rubber, and isoprene rubber, and hydrogenated products thereof, styrene-butadiene block copolymers, styrene-ethylene-butadiene block copolymers, styrene-ethylene-butylene block copolymers, styrene-butadiene-butylene block copolymers, styrene-isoprene block copolymers, styrene-ethylene-propylene block copolymers, and styrene-isobutylene block copolymers, and hydrogenated products thereof. Examples of the elastomer-based resin include polyolefin-based elastomers, which are an embodiment of polyolefin-based resins, polyamide-based elastomers, which are an embodiment of polyamide-based resins, and polyester-based elastomers, which are an embodiment of polyester-based resins.

[0105] <Polyphenylene ether> The resin composition of the present embodiment contains polyphenylene ether in addition to the thermoplastic resin described above. In one aspect, the polyphenylene ether is a polyphenylene ether (low Tg polyphenylene ether) having a glass transition temperature of −100° C. to 50° C. as measured by a differential scanning calorimeter (DSC). The glass transition temperature of the polyphenylene ether refers to the peak top temperature of an endothermic peak that appears when the temperature is increased from −90° C. at a rate of 10° C. / min using the DSC. The detailed procedure will be described later.

[0106] In one embodiment, the polyphenylene ether has a glass transition temperature of -100°C or higher, preferably -80°C or higher, and more preferably -50°C or higher. If the polyphenylene ether has a glass transition temperature of -100°C or higher, the resin composition can exhibit good heat resistance. In one embodiment, the polyphenylene ether has a glass transition temperature of 50°C or lower, preferably 25°C or lower, and more preferably -5°C or lower, by DSC. If the polyphenylene ether has a glass transition temperature of 50°C or lower, the aggregation of cellulose nanofibers can be suppressed when the cellulose nanofibers and the polyphenylene ether are mixed to produce a resin composition or a dried body, and the mechanical properties of the resin composition can be improved.

[0107] As a method for adjusting the glass transition temperature by DSC, for example, a method for lowering the glass transition temperature by performing molecular design to weaken the interaction between polymer chains and facilitate the movement of the polymer chains is possible. Although not particularly limited, for example, the glass transition temperature can be lowered by introducing a repeating unit having a long-chain alkyl group into polyphenylene ether. In addition, the glass transition temperature by DSC can be adjusted by appropriately adjusting the introduction ratio of the repeating unit having a long-chain alkyl group and / or the chain length of the long-chain alkyl group. In one embodiment, the long-chain alkyl group may be an alkyl group having 2 to 30 carbon atoms. The measuring device for measuring the differential scanning calorimetry is not particularly limited, and a commercially available device can be used. For example, the "DSC250" manufactured by TA Instruments can be used as a differential scanning calorimetry device.

[0108] The polyphenylene ether preferably has, as a side chain, a saturated or unsaturated hydrocarbon group having 7 to 25 carbon atoms, which may be substituted. From the viewpoint of improving the heat resistance of the resin composition of the present embodiment, the polyphenylene ether preferably has, as a side chain, a saturated or unsaturated hydrocarbon group having 20 or less carbon atoms, more preferably having 15 carbon atoms. Furthermore, from the viewpoint of uniformly dispersing the cellulose nanofibers throughout the resin composition during heating and kneading and improving the mechanical properties of the resin composition, the polyphenylene ether preferably has a saturated or unsaturated hydrocarbon group having 8 or more carbon atoms, and even more preferably 9 or more carbon atoms, as a side chain.

[0109] The polyphenylene ether may contain a repeating unit derived from a phenol compound represented by the following formula (1). [ka] In the above formula (1), R 11 and R 12 are each independently a hydrogen atom, a linear saturated hydrocarbon group having 1 to 12 carbon atoms, or a substituent represented by formula (1-1). However, R 11 and R 12 None of the groups can be hydrogen atoms.

[0110] In a preferred embodiment, R 11 and R 12 are each independently a hydrogen atom, a methyl group, an ethyl group, or a substituent represented by formula (1-1). 11 is a substituent represented by formula (1-1). Particularly preferred is R 11 is a substituent represented by formula (1-1), and R 12 is a hydrogen atom. [ka] (In formula (1-1), R 31 are each independently an optionally substituted linear alkyl group having 1 to 8 carbon atoms, or two R 31 The atoms in R are bonded to each other to form a cyclic alkyl group having 1 to 8 carbon atoms. 32 each independently represents an optionally substituted alkylene group having 1 to 8 carbon atoms; each b independently represents 0 or 1; R 33 is a hydrogen atom, an optionally substituted alkyl group having 1 to 8 carbon atoms, or an optionally substituted phenyl group.

[0111] The substituent represented by the above formula (1-1) is preferably a group containing secondary and / or tertiary carbon, such as an isopropyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a tert-amyl group, a 2,2-dimethylpropyl group, a cyclohexyl group, and groups in which the hydrogen of the terminal hydrocarbon group in these groups is replaced with a phenyl group. The substituent represented by the above formula (1-1) is more preferably a tert-butyl group or a cyclohexyl group, and even more preferably a tert-butyl group. The atoms contained in these groups may be bonded to each other to form a ring structure.

[0112] In the resin composition of the present embodiment, R 11 is a t-butyl group, and R 12 is preferably a hydrogen atom.

[0113] In the above formula (1), R 13 is an optionally substituted saturated or unsaturated hydrocarbon group having 15 carbon atoms, preferably R 13 C 15 H 31-2n (each n is independently an integer of 0 to 3).

[0114] Furthermore, the polyphenylene ether may contain a repeating unit derived from a phenol compound of formula (2) in addition to the repeating unit derived from the phenol compound of formula (1). [ka] (In formula (2), R 21 each independently represents an optionally substituted saturated hydrocarbon group having 1 to 6 carbon atoms, an optionally substituted aryl group having 6 to 12 carbon atoms, or a halogen atom; R 22 are each independently a hydrogen atom, an optionally substituted hydrocarbon group having 1 to 6 carbon atoms, an optionally substituted aryl group having 6 to 12 carbon atoms, or a halogen atom.

[0115] In the above formula (2), R 21 are each independently preferably a saturated hydrocarbon group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms, more preferably a methyl group or a phenyl group, and further preferably a methyl group. 21 Preferably, both have the same structure.

[0116] Furthermore, in the above formula (2), R 22 are each independently preferably a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms, more preferably a hydrogen atom or a methyl group. 22 may be the same or different. In a preferred embodiment, two R 22 are both hydrogen atoms, and 22 One of the groups is a hydrogen atom and the other is a hydrocarbon group having 1 to 6 carbon atoms (more preferably a methyl group).

[0117] In this embodiment, the structure of the polyphenylene ether can be identified by analyzing the polyphenylene ether by a technique such as NMR (nuclear magnetic resonance) or mass spectrometry. A specific method for identifying the structure of polyphenylene ether is to carry out field desorption mass spectrometry (FD-MS), which is known to be less prone to fragmentation, and estimate the repeating units based on the intervals between the detected ions. Another method is to combine the FD-MS method with peak analysis of fragment ions by electron ionization (EI) or structural analysis by NMR to estimate the structure of polyphenylene ether. NMR can be used, for example, 1 The structure of the polyphenylene ether may be specifically identified by the method described in the Examples below.

[0118] In addition, the polyphenylene ether preferably has a content ratio of the repeating unit derived from the phenolic compound of the above formula (1) of 20 mol% or more and less than 100 mol%, and a content ratio of the repeating unit derived from the phenolic compound of the above formula (2) of more than 0 mol% and 80 mol% or less, based on the total 100 mol% of the repeating unit derived from the phenolic compound of the above formula (1) and the repeating unit derived from the phenolic compound of the above formula (2). From the viewpoint of uniformly dispersing the cellulose nanofibers throughout the resin composition during heat kneading and improving the mechanical properties of the resin composition, the content ratio of the repeating unit derived from the phenolic compound of the above formula (1) of 100 mol% of the repeating unit derived from the phenolic compound of the above formula (1) and the repeating unit derived from the phenolic compound of the above formula (2) is preferably 20 mol% or more, or 30 mol% or more, or 40 mol% or more, or 50 mol% or more. In addition, from the viewpoint of further exhibiting the heat resistance of the resin composition of this embodiment, the content ratio of the repeating unit derived from the phenol compound of the above formula (1) relative to the total 100 mol% of the repeating unit derived from the phenol compound of the above formula (1) and the repeating unit derived from the phenol compound of the above formula (2) is preferably less than 100 mol%, or 95 mol% or less, or 90 mol% or less, or 85 mol% or less.

[0119] In this embodiment, the total molar ratio of the repeating units derived from the phenol compound of the above formula (1) and the repeating units derived from the phenol compound of the above formula (2) relative to 100 mol% of the polyphenylene ether is preferably 80 mol% or more, more preferably 90 mol% or more, and even more preferably 95 mol% or more, and may be 100 mol%.

[0120] The molar ratio of the repeating units derived from the phenol compound of the above formula (1) and the molar ratio of the repeating units derived from the phenol compound of the above formula (2) relative to the total of 100 mol % of the repeating units derived from the phenol compound of the above formula (1) and the repeating units derived from the phenol compound of the above formula (2) are, for example,1 H-NMR, 13 It can be determined by an analytical method such as C-NMR, and more specifically, it is measured by the method described in the Examples below.

[0121] In addition, since the phenolic compound of the above formula (2) does not have an unsubstituted ortho position (i.e., since no hydrogen atoms are bonded to the two carbon atoms at the ortho positions relative to the carbon atom to which the hydroxyl group is bonded), it can react with another phenolic monomer predominantly at the carbon atoms at the para positions to the phenolic hydroxyl group. Therefore, the repeating unit derived from the phenolic compound of the above formula (2) includes a repeating unit having the structure of the following formula (2a). [ka] (In formula (2a), R 21 and R 22 is R in Eq. (2) 21 and R 22 are the same as

[0122] The content of the repeating unit having the structure of formula (2a) in the repeating unit derived from the phenol compound of formula (2) above is preferably 90% or more, more preferably 95% or more, even more preferably 99% or more, and may be 100%.

[0123] On the other hand, R of the phenol compound of the above formula (1) 11 and R 12 are each independently a hydrogen atom, a linear saturated hydrocarbon group having 1 to 12 carbon atoms, or a substituent represented by the above formula (1-1) (provided that R 11 and R 12 None of the groups can be hydrogen atoms), R 11 and R 12 When either of is a hydrogen atom, in addition to the phenolic hydroxyl group, it may react with another phenolic monomer at the ortho or para position of the phenolic compound. Therefore, the repeating unit derived from the phenol compound of the above formula (1) can include at least one selected from the group consisting of a structural unit of the following formula (1a), a structural unit of the following formula (1b), and a structural unit of the following formula (1c). [ka] [ka] [ka] (R in formula (1a), formula (1b), and formula (1c) 11 , R 12 , and R 13 is R in the above formula (1). 11 , R 12 , and R 13 are the same as

[0124] In the repeating units derived from the phenol compound of formula (1), the total content on a molar basis of the structural units of formula (1a), (1b), and (1c) is preferably 90% or more, more preferably 95% or more, and even more preferably 99% or more, and may be 100%.

[0125] In the present embodiment, from the viewpoint of obtaining fluidity for uniformly dispersing the cellulose nanofibers throughout the resin composition during heating and kneading, the polyphenylene ether preferably has a weight average molecular weight of 150,000 or less, more preferably 100,000 or less, and even more preferably 80,000 or less. In addition, from the viewpoint of improving the heat resistance and mechanical properties of the resin composition, the weight average molecular weight is preferably 1,000 or more, more preferably 2,000 or more, and even more preferably 4,000 or more. The weight average molecular weight is measured using gel permeation chromatography in terms of standard polystyrene.

[0126] The polyphenylene ether preferably has a viscosity of 1 mPa·s to 1,000,000 mPa·s at 80°C. From the viewpoint of uniformly dispersing the cellulose nanofibers throughout the resin composition during heat kneading and improving the mechanical properties of the resin composition, the viscosity of the polyphenylene ether at 80°C is more preferably 500,000 mPa·s or less, and even more preferably 300,000 mPa·s or less. The viscosity is measured with a B-type viscometer.

[0127] The polyphenylene ether preferably has a thermal decomposition onset temperature of 300° C. or higher. From the viewpoint of uniformly dispersing the cellulose nanofibers throughout the resin composition during heat kneading and improving the mechanical properties of the resin composition, the polyphenylene ether more preferably has a thermal decomposition onset temperature of 320° C. or higher, and further preferably has a thermal decomposition onset temperature of 340° C. or higher. From the viewpoint of ease of production of the polyphenylene ether, in one embodiment, the thermal decomposition onset temperature of the polyphenylene ether may be 500° C. or lower, or 450° C. or lower, or 400° C. or lower. In the present disclosure, the thermal decomposition onset temperature of polyphenylene ether is the 5% weight loss temperature in the thermal decomposition onset temperature analysis under nitrogen flow described below.

[0128] The polyphenylene ether in the present embodiment may have at least one partial structure selected from the group consisting of a partial structure of the following formula (3a), a partial structure of the following formula (3b), a partial structure of the following formula (3c), and a partial structure of the following formula (3d). [ka] [ka] [ka] (In formula (3c), R 4 is a hydrogen atom or a saturated or unsaturated hydrocarbon group having 1 to 10 carbon atoms, and the saturated or unsaturated hydrocarbon is R 4 may have a substituent within the range of a total carbon number of 1 to 10.) [ka] (In formula (3d), R 5 is a saturated or unsaturated divalent hydrocarbon group having 1 to 10 carbon atoms, and the saturated or unsaturated divalent hydrocarbon is R 5 may have a substituent within a range in which the total carbon number of R is 1 to 10; 6 is a hydrogen atom or a saturated or unsaturated hydrocarbon group having 1 to 10 carbon atoms, and the saturated or unsaturated hydrocarbon is R 6 may have a substituent within the range of a total carbon number of 1 to 10.)

[0129] (Production method of polyphenylene ether) The polyphenylene ether of the present embodiment can be obtained, for example, by a method including at least a step of oxidatively polymerizing a monovalent raw material phenol containing the phenol compound of the above formula (1). The step of oxidatively polymerizing is preferably a step of oxidatively polymerizing raw material phenol containing the phenol compound of the above formula (1) and the phenol compound of the above formula (2).

[0130] Examples of the phenol compound of the above formula (1) include 3-pentadecylphenol, commercially available cardanol, modified 3-pentadecylphenol obtained by introducing a linear saturated hydrocarbon group having 1 to 12 carbon atoms or a substituent represented by the above formula (1-1) into 3-pentadecylphenol, and modified cardanol obtained by introducing a linear saturated hydrocarbon group having 1 to 12 carbon atoms or a substituent represented by the above formula (1-1) into commercially available cardanol. From the viewpoint of suppressing multi-branching and suppressing gelation, examples of the substituent to be introduced into the 3-pentadecylphenol or commercially available cardanol include R 11 or by introducing a bulky substituent, such as a tert-butyl group or a cyclohexyl group, into R 11 and R 12 It is preferable to introduce a methyl group into both R 11 and R 12 Examples of a method for introducing a substituent into include A) a method of reacting with an alkyl halide in the presence of a Lewis acid, and B) a method of reacting with isobutene or the like in the presence of a Bronsted acid. The phenol compound of formula (1) may be used alone or in combination of two or more kinds.

[0131] Examples of the phenol compound of the above formula (2) include 2,6-dimethylphenol, 2-methyl-6-ethylphenol, 2,6-diethylphenol, 2-ethyl-6-n-propylphenol, 2-methyl-6-chlorophenol, 2-methyl-6-bromophenol, 2-methyl-6-n-propylphenol, 2-ethyl-6-bromophenol, 2-methyl-6-n-butylphenol, 2,6-di-n-propylphenol, 2-ethyl-6-chlorophenol, 2-methyl-6-phenylphenol, 2,6-diphenylphenol, 2-methyl-6-tolylphenol, 2,6-ditolylphenol, 2,3,6-trimethylphenol, 2,3-diethyl-6-n-propylphenol, 2,3,6-tributylphenol, 2,6-di-n-butyl-3-methylphenol, 2,6-dimethyl-3-n-butylphenol, and 2,6-dimethyl-3-t-butylphenol. Among these, 2,6-dimethylphenol, 2,3,6-trimethylphenol, and 2,6-diphenylphenol are particularly preferred because they are inexpensive and easily available. The phenol compound of the above formula (2) may be used alone or in combination of two or more kinds.

[0132] In the oxidation polymerization step, an aromatic solvent that is a good solvent for polyphenylene ether may be used as the polymerization solvent, for example, aromatic hydrocarbons such as benzene, toluene, xylene (including o-, m-, and p-isomers), and ethylbenzene; halogenated hydrocarbons such as chlorobenzene and dichlorobenzene; nitro compounds such as nitrobenzene; etc. On the other hand, the polymerization can also be carried out in a poor solvent such as alcohol.

[0133] In the oxidative polymerization step, a known polymerization catalyst that can generally be used for the production of polyphenylene ether, such as a copper compound, a halogen compound, and / or an amine compound, may be used. Examples of the polymerization catalyst include a combination of a copper compound and an amine compound; a manganese compound and an amine compound; or a cobalt compound and an amine compound. In order to efficiently proceed with the polymerization reaction, an alkali or a further amine compound may be added to the polymerization catalyst.

[0134] In the oxidative polymerization step, a surfactant may be added to improve the reaction efficiency. Examples of the surfactant include trioctylmethylammonium chloride, known under the trade names Aliquat 336 and Capriquat. The amount of the surfactant used is preferably not more than 0.1% by mass relative to the total amount (100% by mass) of the polymerization reaction mixture.

[0135] The oxidative polymerization step may be carried out in an oxygen-containing gas. As the oxygen-containing gas, pure oxygen, a mixture of oxygen and an inert gas such as nitrogen in any ratio, air, a mixture of air and an inert gas such as nitrogen in any ratio, etc. can be used. The pressure in the system during the polymerization reaction is sufficient at normal pressure, but may be reduced or increased as necessary.

[0136] The polymerization temperature is not particularly limited, but if it is too low, the reaction will not proceed easily, and if it is too high, the reaction selectivity may decrease or gel may be formed, so it is preferably in the range of 0°C to 60°C or 10°C to 40°C.

[0137] After the polymerization reaction is completed, post-treatment may be performed. Usually, an acid such as hydrochloric acid or acetic acid, ethylenediaminetetraacetic acid (EDTA) or a salt thereof, or nitrilotriacetic acid or a salt thereof is added to the reaction solution to deactivate the catalyst. In addition, a dihydric phenol by-product generated by polymerization of polyphenylene ether may be removed by a conventionally known method. If the metal ion as the polymerization catalyst is substantially deactivated, the reaction solution is decolorized by simply heating it. Decolorization is also possible by adding a required amount of a known reducing agent, such as hydroquinone or sodium dithionite, to the reaction solution. Compounds generated by deactivating the polymerization catalyst may be removed by a known method, such as extraction. The reaction solution may be concentrated or dried by a known method. The drying temperature is preferably 60° C. or higher, 80° C. or higher, or 110° C. or higher from the viewpoint of efficiently removing high-boiling volatile components, and may be 400° C. or lower in one embodiment from the viewpoint of maintaining the quality of the polyphenylene ether.

[0138] Polyphenylene ethers can also be produced by a redistribution reaction in which a polyphenylene ether derived from a phenolic compound of formula (2) is equilibrated with a phenolic compound of formula (1) in the presence of an oxidizing agent. Redistribution reactions are known in the art and are described, for example, in U.S. Patent No. 3,496,236 to Cooper et al. and U.S. Patent No. 5,880,221 to Liska et al.

[0139] When the polyphenylene ether is a modified polyphenylene ether, the method of introducing a functional group into the hydroxyl group of the unmodified polyphenylene ether is not limited, and for example, it can be obtained by a reaction of forming an ester bond between the hydroxyl group of the unmodified polyphenylene ether and a carboxylic acid having a carbon-carbon double bond (hereinafter, carboxylic acid). The ester bond can be formed, for example, by a. a reaction between a carboxylic acid halide and a hydroxyl group at the polymer end, b. a reaction between a carboxylic acid anhydride and a hydroxyl group at the polymer end, c. a direct reaction between a carboxylic acid and a hydroxyl group at the polymer end, d. an ester exchange reaction, etc.

[0140] The reaction of the carboxylic acid halide of a with the hydroxyl group at the polymer end is one of the most common methods. Although chlorides or bromides are generally used as the carboxylic acid halide, other halides may also be used. The reaction may be a direct reaction between the hydroxyl group and the carboxylic acid halide, or a reaction between the hydroxyl group and an alkali metal salt of the carboxylic acid halide. Since the direct reaction between the carboxylic acid halide and the hydroxyl group generates an acid such as hydrogen halide, a weak base such as an amine may be present in order to trap the acid.

[0141] In the reaction of a carboxylic acid anhydride with a hydroxyl group (b) and the direct reaction of a carboxylic acid with a hydroxyl group (c), a compound such as a carbodiimide or dimethylaminopyridine may be allowed to coexist in order to activate the reaction site and promote the reaction.

[0142] In the case of the transesterification reaction of d, it is desirable to remove the generated alcohols as necessary. In addition, known metal catalysts may be used to promote the reaction. After the reaction, the reaction mixture may be washed with water or an acidic or alkaline aqueous solution to remove by-products such as amine salts, or the polymer solution may be dropped into a poor solvent such as alcohols to recover the target product by reprecipitation. After washing the polymer solution, the solvent may be distilled off under reduced pressure to recover the polymer.

[0143] In addition, polyphenylene ether may be obtained by oxidatively polymerizing 3-pentadecylphenol or commercially available cardanol, and optionally 2,6-dimethylphenol as the phenolic compound of formula (2), and then introducing at least one partial structure selected from the group consisting of formulas (3a), (3b), (3c), and (3d) into the obtained polymer. The polyphenylene ether of this embodiment may be obtained by oxidatively polymerizing modified 3-pentadecylphenol or modified cardanol as the phenolic compound of formula (1), and optionally 2,6-dimethylphenol as the phenolic compound of formula (2). Furthermore, the polyphenylene ether of the present embodiment may be obtained by oxidatively polymerizing modified 3-pentadecylphenol or modified cardanol as the phenol compound of formula (1), and optionally 2,6-dimethylphenol as the phenol compound of formula (2), and then introducing at least one partial structure selected from the group consisting of formulas (3a), (3b), (3c), and (3d) into the obtained polymer.

[0144] <Dispersion aid> In one aspect, the resin composition of the present embodiment does not contain a surfactant. Low Tg polyphenylene ether tends to have better thermal stability than, for example, non-polymer surfactants, and is therefore advantageous in that even if the resin composition is heated during production and processing, it does not adversely affect the mechanical properties of the resin composition and the molded product. The resin composition according to one aspect may be surfactant-free because good dispersion of cellulose nanofibers can be achieved even without surfactant due to the contribution of low Tg polyphenylene ether. In the present disclosure, surfactant-free means that the amount of surfactant in the resin composition is less than 0.1 parts by mass relative to 100 parts by mass of low Tg polyphenylene ether. On the other hand, in one aspect, a small amount of a dispersion aid may be contained in order to modify the surface of the cellulose nanofiber through interaction and further improve the dispersion of the cellulose nanofiber by the low Tg polyphenylene ether. In this case, the dispersion aid may be contained in an amount of preferably 0.1 part by mass or more, or 1 part by mass or more, or 5 parts by mass or more, relative to 100 parts by mass of the low Tg polyphenylene ether, from the viewpoint of improving the dispersibility of the cellulose nanofibers, and may be contained in an amount of preferably 50 parts by mass or less, or 30 parts by mass or less, or 10 parts by mass or less, from the viewpoint of performance degradation caused by the dispersion aid. In one embodiment, it is further preferable that the dispersion aid has a hydrophilic segment and a hydrophobic segment in the same molecule (i.e., is an amphiphilic molecule), from the viewpoint of dispersing the fine cellulose fibers more uniformly in the resin.

[0145] <Additional Ingredients> The resin composition may further contain additional components as necessary to improve its performance. Examples of the additional components include filler components other than cellulose nanofibers, such as glass fibers, carbon fibers, and organic fibers (such as aramid fibers); compatibilizers; plasticizers; polysaccharides such as starches and alginic acid; natural proteins such as gelatin, glue, and casein; inorganic compounds such as zeolite, ceramics, talc, silica, metal oxides, and metal powders; colorants; fragrances; pigments; flow regulators; leveling agents; conductive agents; heat stabilizers; antioxidants; antistatic agents; ultraviolet absorbers; ultraviolet dispersants; and deodorants. The content ratio of any additional component in the resin composition is appropriately selected within a range that does not impair the desired effects of the present invention, and may be, for example, 0.01 to 50% by mass, or 0.1 to 30% by mass.

[0146] The low Tg polyphenylene ether may be combined with the cellulose nanofiber to form a masterbatch, in which the mass ratio of the cellulose nanofiber / low Tg polyphenylene ether may be 0.1 / 99.9 to 99.9 / 0.1, or 1 / 99 to 99 / 1, or 5 / 95 to 95 / 5, or 10 / 90 to 90 / 10, or 20 / 80 to 80 / 20, or 30 / 70 to 70 / 30, or 40 / 60 to 60 / 40.

[0147] The master batch may or may not contain additional components in addition to the cellulose nanofibers and low Tg polyphenylene ether. Examples of the additional components include one or more of the thermoplastic resins exemplified in this disclosure as the thermoplastic resins that may be contained in the resin composition of the present embodiment. The content of the additional components in the master batch is appropriately selected within a range that does not impair the desired effects of the present invention, and may be, for example, 0.01 to 50 mass%, or 0.1 to 30 mass%.

[0148] In the resin composition, the amount of cellulose nanofibers per 100 parts by mass of thermoplastic resin may be, from the viewpoint of the balance between processability and mechanical properties, preferably 0.001 part by mass or more, or 0.01 part by mass or more, or 0.1 part by mass or more, or 1 part by mass or more, and preferably 100 parts by mass or less, or 80 parts by mass or less, or 70 parts by mass or less, or 50 parts by mass or less, or 30 mass% or less.

[0149] In the resin composition, the amount of low Tg polyphenylene ether per 100 parts by mass of the thermoplastic resin may be, from the viewpoint of the balance between processability and mechanical properties, preferably 0.001 part by mass or more, or 0.01 part by mass or more, or 0.1 part by mass or more, or 1 part by mass or more, and preferably 100 parts by mass or less, or 80 parts by mass or less, or 70 parts by mass or less, or 50 parts by mass or less, or 30% by mass or less, or 10% by mass or less, or 8 parts by mass or less.

[0150] The amount of cellulose nanofibers relative to 100% by mass of the resin composition may be, from the viewpoint of the balance between processability and mechanical properties, preferably 0.001% by mass or more, or 0.01% by mass or more, or 0.1% by mass or more, or 1% by mass or more, and preferably 50% by mass or less, or 40% by mass or less, or 30% by mass or less, or 20% by mass or less.

[0151] In the resin composition, the content of cellulose nanofibers relative to 100% by mass of the total of cellulose nanofibers and low Tg polyphenylene ether is preferably 0.5% by mass or more, or 1% by mass or more, or 3% by mass or more, from the viewpoint of obtaining a good reinforcing effect of the cellulose nanofibers, and is preferably 80% by mass or less, or 60% by mass or less, or 33% by mass or less, or 30% by mass or less, or 20% by mass or less, or 10% by mass or less, from the viewpoint of obtaining good advantages from the use of the low Tg polyphenylene ether.

[0152] The thermal decomposition onset temperature T1 of the low Tg polyphenylene ether and the thermal decomposition onset temperature T2 of the cellulose nanofiber preferably satisfy the following relationship in terms of good mechanical properties of the resin composition and the molded article: (T1) ≧ (T2) Meet the following.

[0153] The thermal decomposition onset temperature T1 of the low Tg polyphenylene ether and the temperature T3 which is the melting point or the glass transition temperature + 70° C. of the thermoplastic resin preferably satisfy the following relationship in terms of good mechanical properties of the resin composition and the molded article: (T1)>(T3) Meet the following. T3 is the melting point if the thermoplastic resin is a crystalline resin, and is the glass transition temperature +70°C if the thermoplastic resin is an amorphous resin. In a particularly preferred embodiment, the thermoplastic resin is a thermoplastic resin having crystallinity (i.e., having a melting point), and the temperature T3 is the melting point of the thermoplastic resin.

[0154] The thermal decomposition onset temperature T1 of the low Tg polyphenylene ether and the temperature T4 which is the melting point or the glass transition temperature + 100° C. of the thermoplastic resin preferably satisfy the following relationship in terms of good mechanical properties of the resin composition and the molded article: (T1)>(T4) Meet the following. T4 is the melting point if the thermoplastic resin is a crystalline resin, and is the glass transition temperature +100°C if the thermoplastic resin is an amorphous resin.

[0155] In a particularly preferred embodiment, the thermal decomposition onset temperature T1 of the low Tg polyphenylene ether, the thermal decomposition onset temperature T2 of the cellulose nanofiber, and the temperature T3 which is the melting point of the thermoplastic resin or the glass transition temperature + 70° C., satisfy the following relationship in terms of good mechanical properties of the resin composition and the molded article: (T1) ≧ (T2) > (T3) Meet the following.

[0156] In one aspect, the difference T1-T2 between the above T1 and the above T2 is preferably 5°C or more, or 10°C or more, or 30°C or more from the viewpoint of avoiding process constraints resulting from the use of low Tg polyphenylene ether because low Tg polyphenylene ether is less susceptible to thermal degradation than cellulose nanofibers, and is preferably 200°C or less, or 150°C or less, or 100°C or less from the viewpoint of easy availability of low Tg polyphenylene ether.

[0157] In one aspect, the difference T1-T3 between the above T1 and the above T3 is, from the viewpoint of avoiding thermal degradation of the low Tg polyphenylene ether due to heating during production and processing of the resin composition and improving the mechanical properties of the resin composition and the molded article obtained by molding the same, preferably 30°C or more, or 50°C or more, or 70°C or more, and from the viewpoint of easily selecting a resin that imparts good mechanical properties to the resin composition and the molded article, preferably 200°C or less, or 150°C or less, or 100°C or less.

[0158] In one aspect, the difference T2-T3 between the above T2 and the above T3 is preferably 30°C or more, or 50°C or more, or 70°C or more, from the viewpoint of avoiding thermal degradation of the cellulose nanofiber due to heating during the production and processing of the resin composition and improving the mechanical properties of the resin composition and the molded article obtained by molding it, and is preferably 200°C or less, or 150°C or less, or 100°C or less, from the viewpoint of easily selecting a resin that imparts good mechanical properties to the resin composition and the molded article.

[0159] In one aspect, the difference T1-T4 between the above T1 and the above T4 is, from the viewpoint of avoiding thermal degradation of the low Tg polyphenylene ether due to heating during production and processing of the resin composition and improving the mechanical properties of the resin composition and the molded article obtained by molding it, preferably higher than 0°C, or 20°C or higher, or 40°C or higher, and from the viewpoint of easily selecting a resin that imparts good mechanical properties to the resin composition and the molded article, preferably 170°C or lower, or 120°C or lower, or 70°C or lower.

[0160] In one aspect, the difference T2-T4 between the above T2 and the above T4 is, from the viewpoint of avoiding thermal degradation of the cellulose nanofibers due to heating during the production and processing of the resin composition and improving the mechanical properties of the resin composition and the molded article obtained by molding it, preferably greater than 0°C, or 20°C or more, or 40°C or more, and from the viewpoint of easily selecting a thermoplastic resin that imparts good mechanical properties to the resin composition and the molded article, preferably 170°C or less, or 120°C or less, or 70°C or less.

[0161] <Method for producing resin composition> One aspect of the present invention also provides a method for producing a resin composition containing cellulose nanofibers, a thermoplastic resin, and a low Tg polyphenylene ether. In one aspect, the method includes heating and kneading a mixture containing cellulose nanofibers, a thermoplastic resin, and a low Tg polyphenylene ether. In one aspect, the mixture may be obtained by mixing the dried body of the present disclosure containing cellulose nanofibers and a low Tg polyphenylene ether, a thermoplastic resin, and optionally additional components. The low Tg polyphenylene ether can function as a dispersant for dispersing cellulose nanofibers well in a resin, and tends to have excellent cellulose nanofiber aggregation suppression ability and heat resistance compared to, for example, non-polymer materials. By using such a low Tg polyphenylene ether, when producing the resin composition of this embodiment, heat kneading can be sufficiently performed without concern for thermal deterioration of each component, so that the cellulose nanofibers can be well dispersed in the thermoplastic resin. The resin composition produced in this manner is advantageous for forming a molded product with excellent mechanical properties.

[0162] Examples of the heat kneading method include a method of previously preparing a masterbatch containing cellulose nanofibers and a low Tg polyphenylene ether and kneading it with a thermoplastic resin, a method of simultaneously or sequentially feeding the cellulose nanofibers, the thermoplastic resin, and the low Tg polyphenylene ether into a kneader and kneading them, etc. In one embodiment, the masterbatch may be the dried product of the present disclosure containing the cellulose nanofibers and the low Tg polyphenylene ether.

[0163] The heating and kneading method is as follows: A method in which cellulose nanofibers, low Tg polyphenylene ether, and any additional components are mixed to produce a master batch, which is then mixed with a thermoplastic resin monomer to carry out a resin polymerization reaction, the resulting resin composition is extruded into a strand shape, and cooled and solidified in a water bath to obtain a pellet-shaped molded product; - a method in which a mixture of a thermoplastic resin and the above master batch is melt-kneaded using a single-screw or twin-screw extruder, extruded into a strand shape, and cooled and solidified in a water bath to obtain a pellet-shaped molded product; - a method in which a mixture of a thermoplastic resin and the above masterbatch is melt-kneaded using a single-screw or twin-screw extruder, extruded into a rod or tube, and cooled to obtain an extrusion molded product; A method of melt-kneading a mixture of a thermoplastic resin and the above masterbatch using a single-screw or twin-screw extruder, and extruding the mixture through a T-die to obtain a sheet or film-like molded product; In a preferred embodiment, a mixture of a thermoplastic resin and a master batch is melt-kneaded using a single-screw or twin-screw extruder, extruded into a strand shape, and cooled and solidified in a water bath to obtain a pellet-shaped molded product. For example, a master batch that has been delivered so as to have a desired ratio with the thermoplastic resin may be added to and mixed with the thermoplastic resin, and then the mixture may be melt-kneaded.

[0164] The master batch can be produced by mixing the components constituting the master batch using a stirring means such as a rotation / revolution mixer, a planetary mixer, a homogenizer, a propeller type stirrer, a rotary stirrer, an electromagnetic stirrer, an open roll, a Banbury mixer, a single screw extruder, or a twin screw extruder. In addition, the mixture may be stirred under heating in order to efficiently perform shearing. Mixing using a homogenizer is preferred because it can promote dispersion by applying high shearing force and pressure. The order of addition of the components during mixing is not limited, but for example, (1) A method of simultaneously adding and mixing cellulose nanofibers, low Tg polyphenylene ether, and optionally additional components; (2) A method in which components other than the low Tg polyphenylene ether are mixed in advance to obtain a premixture, and then the premixture is mixed with the low Tg polyphenylene ether; etc.

[0165] For the melt kneading to obtain the resin composition, an extruder such as a single screw extruder or a twin screw extruder can be used as described above, but a twin screw extruder is preferred in terms of controlling the dispersibility of the cellulose nanofibers. The L / D ratio, obtained by dividing the cylinder length (L) of the extruder by the screw diameter (D), is preferably 30 or more, and particularly preferably 40 or more. The screw rotation speed during kneading is preferably in the range of 50 to 800 rpm, and more preferably in the range of 100 to 600 rpm.

[0166] Each screw in the cylinder of the extruder is optimized by combining a conveying screw with an elliptical two-wing screw shape, a kneading element called a kneading disk, and the like.

[0167] The minimum processing temperatures recommended by thermoplastic resin suppliers are 255 to 270°C for polyamide 66, 225 to 240°C for polyamide 6, 225 to 240°C for polybutylene terephthalate, 170 to 190°C for polyacetal resin, and 160 to 180°C for polypropylene. The heating temperature setting is preferably in the range of 20°C higher than these recommended minimum processing temperatures. By setting the mixing temperature in this temperature range, the cellulose nanofibers and the resin can be mixed uniformly.

[0168] <Shape of resin composition> The resin composition of the present embodiment can be provided in various shapes. Specifically, resin pellets, sheets, fibers, plates, rods, etc. can be mentioned, but the resin pellet shape is preferred from the viewpoint of ease of post-processing and ease of transportation. Preferred resin pellet shapes include round, elliptical, and cylindrical shapes, and the shape may vary depending on the cutting method used during extrusion processing. For example, pellets cut by a cutting method called underwater cutting are often round, pellets cut by a cutting method called hot cutting are often round or elliptical, and pellets cut by a cutting method called strand cutting are often cylindrical. The preferred pellet diameter of round pellets is 1 mm or more and 3 mm or less. The preferred diameter of cylindrical pellets is 1 mm or more and 3 mm or less, and the preferred length is 2 mm or more and 10 mm or less. It is desirable to set the above diameter and length to be equal to or greater than the lower limit from the viewpoint of operational stability during extrusion, and it is desirable to set them to be equal to or less than the upper limit from the viewpoint of bite into the molding machine during post-processing.

[0169] ≪Molded products≫ The resin composition may be molded into a desired shape alone or together with other components to produce a desired molded product. The method of combining the components and the molding method are not particularly limited and may be selected according to the desired molded product. The molding method may include, but is not limited to, injection molding, extrusion molding, blow molding, inflation molding, and foam molding. The injection molding method is particularly preferred from the viewpoints of design and cost.

[0170] In one embodiment, the molding method may be a profile molding. That is, in one embodiment, the molded article of the present embodiment may be a profile molded article. One aspect of the present invention also provides a method for producing a profile extrusion molded article, comprising a step of profile extruding the resin composition of the present embodiment.

[0171] A known method can be used for the contour extrusion molding. A specific example of the contour extrusion molding method is to feed a resin composition into an extrusion molding machine, knead it while heating it inside, and extrude it from a contour extrusion die to obtain an uncooled molded product. The uncooled molded product is then continuously guided to a cooling zone and cooled to obtain a contour extrusion molded product. Another example is a method in which melt kneading is performed to obtain a resin composition, and then the resin composition is extruded using a die of the kneading machine as a die for profile extrusion to obtain an uncooled molded product, and then the uncooled molded product is continuously guided to a cooling zone to be cooled to obtain a profile extrusion molded product.

[0172] The lower limit of the extrusion temperature during profile extrusion is preferably +5°C, more preferably +10°C, relative to the melting point when the thermoplastic resin in the resin composition is a crystalline resin, or +10°C, more preferably relative to the glass transition point when the thermoplastic resin in the resin composition is an amorphous resin. By controlling the lower limit within this range, the productivity of profile extrusion can be improved. The upper limit of the extrusion temperature during profile extrusion is preferably +100°C, more preferably +80°C, more preferably +70°C, and more preferably +60°C, relative to the melting point when the thermoplastic resin in the resin composition is a crystalline resin, or +100°C, more preferably +80°C, more preferably +70°C, and more preferably +60°C, respectively, relative to the glass transition point when the thermoplastic resin in the resin composition is an amorphous resin. By controlling the upper limit within this range, the deterioration of the cellulose nanofiber can be suppressed, so that the mechanical properties of the resin composition can be maintained, and the drawdown of the resin between the profile extrusion die and the cooling zone can be suppressed, so that the dimensional accuracy of the profile extrusion molded product is good.

[0173] The cross-sectional shape of the irregular extrusion molding is not particularly limited, but the cross-sectional shape is preferably a sheet shape, a pipe shape, a tube shape, a square shape, or the like. In the case of a sheet shape, the sheet thickness can be 0.2 to 50 mm, and the sheet width can be 10 to 1500 mm. In the case of a pipe or tube shape, the thickness can be 0.1 to 30 mm, and the inner diameter can be 1 to 1000 mm. In the case of a square shape, the angle of the corner can be 30 to 150 degrees. In addition, the minimum curvature radius of the valley side of the corner can be 0.1 mm.

[0174] <Applications of resin composition and molded products> The resin composition of the present embodiment is useful as a substitute for steel plates, fiber-reinforced plastics (e.g., carbon fiber-reinforced plastics, glass fiber-reinforced plastics, etc.), resin composites containing inorganic fillers, etc. Suitable applications of the resin composition include industrial machine parts, general machine parts, automobile, railway, vehicle, ship, and aerospace-related parts, electronic and electrical parts, building and civil engineering materials, daily necessities, sports and leisure goods, wind power generation housing members, containers and packaging members, etc. For example, the above-mentioned irregular shapes are suitable for applications such as rails, pipes, sashes, door frames, window frames, handrails, deck materials, fences, and various building materials.

[0175] <3D printing materials> A preferred example of the use of the resin composition of this embodiment is a modeling material for 3D printing. One aspect of the present invention provides a modeling material for 3D printing that is composed of the resin composition of this embodiment. The modeling material for 3D printing may be formed into a desired form selected from various forms such as pellets, filaments, and powder. In one aspect, the modeling material for 3D printing has the form of a filament or powder.

[0176] The 3D printing modeling material of this embodiment is advantageous in that it suppresses the generation of decomposition gases and the like during the processing of the 3D printing modeling material due to the contribution of the high cellulose nanofiber aggregation suppression ability and high heat resistance of the low Tg polyphenylene ether, and can also be advantageous in improving the adhesive properties between modeling materials by suppressing the aggregation of cellulose nanofibers, optimizing the fluidity of the modeling material during processing, etc. The low Tg polyphenylene ether can also have the advantage of less bleeding onto the surface of the 3D printing modeling material or the modeled object.

[0177] The 3D printing modeling material of this embodiment is advantageous in that it suppresses dripping (drawdown) due to its own weight from the nozzle during molding or modeling, due to the high cellulose nanofiber aggregation inhibitory ability of the low Tg polyphenylene ether.

[0178] A known method can be used to mold the resin composition into a desired shape of a 3D printing material. For example, the filament may be a monofilament or a multifilament, but a monofilament is preferred because of ease of molding.

[0179] The diameter of the filamentary modeling material is preferably 0.5 to 5.0 mm, more preferably 1.0 to 3.5 mm, and most preferably 1.5 to 3.0 mm. The length of the filamentary modeling material is preferably more than 1 m, more preferably more than 10 m, more preferably more than 100 m, and most preferably more than 300 m. By controlling the shape of the filamentary modeling material within this range, it becomes possible to widely select applicable 3D printers, and it becomes possible to appropriately design the modeling time, the size and sophistication of the modeled object. In one embodiment, the length of the filamentary modeling material may be 20,000 m or less.

[0180] In one embodiment, the filament-shaped shaping material can be produced by heating and melting the resin composition, passing it through a fine hole such as a nozzle, cooling it, and winding it up. The diameter of the fine hole can be appropriately selected according to the diameter of the filament and the winding speed, but from the viewpoint of production efficiency and the frequency of occurrence of thread breakage, it is preferably 0.5 to 10.0 mm, more preferably 0.8 to 5.0 mm, and most preferably 1.0 to 3.0 mm. As a cooling method, a known method such as air cooling or water cooling can be appropriately selected, but air cooling is preferred from the viewpoint of preventing water absorption due to the hydrophilicity of cellulose nanofibers. The winding speed of the filament is preferably 0.1 to 10 m / sec, more preferably 0.15 to 5 m / sec, and most preferably 0.2 to 1 m / sec, from the viewpoint of production efficiency and the frequency of occurrence of thread breakage. The manufacturing device for the filament-shaped shaping material and the manufacturing device for the resin composition may be the same or different.

[0181] The particle size, particle shape, and aspect ratio of the powdered modeling material can be appropriately selected according to the 3D printer used. In one embodiment, the particle size is preferably 1 to 10,000 μm, more preferably 10 to 500 μm, and most preferably 30 to 200 μm, from the viewpoint of handling as a modeling material and surface smoothness of the modeled object. The particle shape may be spherical or irregular, but irregular shape is preferable from the viewpoint of suppressing voids during modeling. The aspect ratio is preferably 1.001 to 3.0, preferably 1.01 to 2.0, and most preferably 1.1 to 1.8, from the viewpoint of suppressing voids by reducing interparticle gaps.

[0182] In one embodiment, the powdered modeling material can be produced by pulverizing or reprecipitating the resin composition. The method for pulverizing the resin composition is not particularly limited, and may be wet pulverization, dry pulverization, low-temperature pulverization, freeze pulverization, heat pulverization, etc. A pulverizing medium may be used for the purpose of controlling the shape of the powdered modeling material.

[0183] <Sculpture> One aspect of the present invention provides a molded object produced by molding the resin composition (e.g., resin composition pellets) or 3D printing modeling material of the present embodiment using a 3D printer. Another aspect of the present invention provides a method for producing a molded object, comprising a step of molding the resin composition or 3D printing modeling material of the present embodiment using a 3D printer. Modeling methods for 3D printers include fused deposition modeling, stereolithography, material injection, powder bonding, powder bed fusion, and the like. When a filamentary modeling material is used, the fused deposition modeling is preferred, and when a powdered modeling material is used, the powder bonding and powder bed fusion are preferred.

[0184] <Uses of 3D printing materials and objects> The molded object may be directly applied to various applications, or may be molded into a desired shape alone or together with other components to produce a desired molded product. The method of combining the components and the molding method are not particularly limited and may be selected according to the desired molded product. The molding method may include, but is not limited to, cutting molding, foam molding, etc. The molded object or molded product is useful as a substitute for steel plates, fiber-reinforced plastics (e.g., carbon fiber reinforced plastics, glass fiber reinforced plastics, etc.), resin composites containing inorganic fillers, etc. Suitable applications of 3D printing molding materials, molded objects, or molded products include industrial machine parts, general machine parts, automobiles, railways, vehicles, ships, aerospace-related parts, electronic and electrical parts, building and civil engineering materials, daily necessities, sports and leisure goods, wind power generation housing parts, containers and packaging parts, etc.

[0185] The obtained molded products can be used for a variety of purposes, such as automobile parts, electrical and electronic parts, building materials, lifestyle, cosmetic and medical parts, rails, pipes, sashes, door frames, window frames, handrails, deck materials, fences, and various building materials.

[0186] Specifically, automotive parts include interior parts such as inner handles, fuel trunk openers, seat belt buckles, assist wraps, various switches, knobs, levers, clips, etc., electrical system parts such as meters and connectors, in-vehicle electrical and electronic parts such as audio equipment and car navigation equipment, parts that come into contact with metal such as window regulator carrier plates, door lock actuator parts, mirror parts, wiper motor system parts, fuel system parts and other mechanical parts.

[0187] Electrical and electronic components include parts or components of devices that are made of resin molded products and have many metal contacts, such as audio equipment, video equipment, office automation equipment such as telephones, copy machines, facsimiles, word processors, and computers, and parts or components of toys, specifically chassis, gears, levers, cams, pulleys, bearings, etc.

[0188] Furthermore, it can be suitably used in a wide range of lifestyle-related, cosmetic-related, and medical-related parts, such as lighting fixtures, fittings, piping, cocks, faucets, toilet peripheral parts, and other building materials and piping parts, fasteners, stationery, lip balm and lipstick containers, cleaning devices, water purifiers, spray nozzles, spray containers, aerosol containers, general containers, and syringe needle holders. Among these, it is more preferably usable for gears, which are used in high-temperature environments and subject to high loads.

[0189] <Characteristics of resin composition, 3D printing materials and objects> <Tensile yield strength> In one embodiment, the tensile yield strength of the resin composition, 3D printing modeling material, or modeled object may be 20 MPa or more, or 50 MPa or more, or 80 MPa or more, and may be 300 MPa or less, or 200 MPa or less, or 150 MPa or less.

[0190] <Tensile elongation at break> In one embodiment, the tensile elongation at break of the resin composition, 3D printing modeling material, or modeled object may be 2% or more, or 3% or more, or 5% or more, and may be 200% or less, or 100% or less, or 20% or less.

[0191] <Flexural modulus> In one embodiment, the flexural modulus of the resin composition, 3D printing modeling material, or modeled object may be 2.0 GPa or more, or 2.5 GPa or more, or 3.0 GPa or more, or 3.5 GPa or more, or 3.7 GPa or more, or 3.9 GPa or more, and may be 20.0 GPa or less, or 10.0 GPa or less, or 8.0 GPa or less.

[0192] <250℃ weight loss rate (T 250℃ )> Resin composition, 3D printing material, or modeled object weight loss rate at 250°C (T 250℃From the viewpoint of avoiding thermal degradation during molding of the resin composition and improving the mechanical strength of the molded product, the 250°C weight loss rate is preferably 1.5% or less, or 1.4% or less, or 1.3% or less. It is desirable that the 250°C weight loss rate is low, but from the viewpoint of ease of production of the resin composition, in one embodiment, the 250°C weight loss rate (T 250℃ ) is the weight loss rate when the resin composition is held at 250°C under nitrogen flow for 2 hours in TG analysis. The resin composition is heated from room temperature to 150°C at a heating rate of 10°C / min in a nitrogen flow of 100 ml / min, held at 150°C for 1 hour, then heated from 150°C to 250°C at a heating rate of 10°C / min, and held at 250°C for 2 hours. The weight W0 at the time when 250°C is reached is taken as the starting point, and the weight after holding at 250°C for 2 hours is taken as W1, and is calculated from the following formula. Weight change rate at 250℃ (%): (W1-W0) / W0×100

[0193] <Surface roughness> The resin composition, 3D printing material, or shaped object of the present embodiment has low surface roughness, and thus has excellent decorative properties and appearance. The arithmetic mean surface roughness Ra of the resin composition is preferably 0.5 μm or less, or 0.4 μm or less, or 0.3 μm or less. In one embodiment, the arithmetic mean surface roughness Ra may be 0.001 μm or more, or 0.01 μm or more, or 0.1 μm or more, from the viewpoint of ease of production of the resin composition. EXAMPLES

[0194] The following examples further illustrate exemplary embodiments of the present invention, but the present invention is not limited to these examples.

[0195] Evaluation method <Cellulose nanofiber> [Preparation of porous sheet] First, the concentrated cake was added to tert-butanol, and further dispersed using a mixer or the like until no aggregates were formed. The concentration was adjusted to 0.5% by mass per 0.5 g of cellulose nanofiber solids. 100 g of the resulting tert-butanol dispersion was filtered on filter paper. The filtered material was not peeled off from the filter paper, but was sandwiched together with the filter paper between two sheets of larger filter paper, and dried for 5 minutes in an oven at 150°C while pressing down the edges of the larger filter paper with a weight. The filter paper was then peeled off to obtain a porous sheet with little distortion. The air resistance of this sheet was 10 g / m2. 2 The porous sheets with a permeability of 100 sec / 100 ml or less were used as measurement samples. The basis weight W (g / m2) of the sample left standing for one day in an environment of 23°C and 50% RH 2 After measuring the air permeability, the air permeability resistance R (sec / 100ml) was measured using an Oken air permeability tester (manufactured by Asahi Seiko Co., Ltd., model EG01). 2 The value per unit area was calculated. Weight 10g / m 2 Air resistance per unit (sec / 100ml) = R / W x 10

[0196] [Weight average molecular weight (Mw), number average molecular weight (Mn) and Mw / Mn ratio] 0.88 g of the porous sheet was weighed, cut into small pieces with scissors, lightly stirred, 20 mL of pure water was added, and left for one day. Next, the water and solids were separated by centrifugation. Next, 20 mL of acetone was added, lightly stirred, and left for one day. Next, the acetone and solids were separated by centrifugation. Next, 20 mL of N,N-dimethylacetamide was added, lightly stirred, and left for one day. N,N-dimethylacetamide and solids were separated again by centrifugation, and then 20 mL of N,N-dimethylacetamide was added, lightly stirred, and left for one day. N,N-dimethylacetamide and solids were separated by centrifugation, and 19.2 g of N,N-dimethylacetamide solution prepared so that lithium chloride was 8 mass percent was added to the solids, and it was stirred with a stirrer and confirmed to be dissolved by visual inspection. The solution in which the cellulose nanofibers were dissolved was filtered through a 0.45 μm filter, and the filtrate was used as a sample for gel permeation chromatography. The apparatus and measurement conditions used are as follows. Equipment: Tosoh HLC-8120 Column: TSKgel SuperAWM-H (6.0mm I.D. x 15cm) x 2 Detector: RI detector Eluent: N,N-dimethylacetamide (lithium chloride 0.2%) Flow rate: 0.6mL / min Calibration curve: Pullulan conversion For the acetylated cellulose nanofibers, the weight average molecular weight (Mw), number average molecular weight (Mn), and Mw / Mn ratio of the raw material before acetylation were used.

[0197] [Average content of alkali-soluble polysaccharides] The alkali-soluble polysaccharide content was calculated by subtracting the α-cellulose content from the holocellulose content (Wise method) according to the method described in the non-patent literature (Wood Science Experiment Manual, edited by the Japan Wood Research Society, pages 92-97, 2000) for cellulose nanofibers. The alkali-soluble polysaccharide content was calculated three times for each sample, and the number average of the calculated alkali-soluble polysaccharide contents was taken as the average alkali-soluble polysaccharide content of the cellulose nanofibers. For acetylated cellulose nanofibers, the average alkali-soluble polysaccharide content of the raw material before acetylation was used.

[0198] [Crystallization degree] The porous sheet was subjected to X-ray diffraction measurement, and the crystallinity was calculated according to the following formula. Crystallinity (%)=[I (200) -I (amorphous) ] / I (200) ×100 I (200) : Diffraction peak intensity due to 200 plane (2θ=22.5°) in cellulose I crystal I (amorphous) : The halo peak intensity due to the amorphous phase in cellulose I crystals, which is the peak intensity at an angle 4.5° lower than the diffraction angle of the 200 plane (2θ=18.0°) (X-ray diffraction measurement conditions) Equipment: MiniFlex (Rigaku Corporation) Operation axis 2θ / θ Source CuKα Measurement method: Continuous Voltage 40kV Current 15mA Starting angle 2θ=5° End angle 2θ=30° Sampling width 0.020° Scan speed: 2.0° / min Sample: A porous sheet is attached onto the sample holder.

[0199] [Number average fiber diameter] The concentrated cake was diluted to 0.01% by mass with tert-butanol, dispersed using a high-shear homogenizer (IKA, product name "Ultra Turrax T18") at a rotation speed of 15,000 rpm for 3 minutes, cast onto an osmium-deposited silicon substrate, air-dried, and measured with a high-resolution scanning electron microscope (Hitachi High-Tech, Regulus 8220). The measurement was performed by adjusting the magnification so that at least 100 cellulose fibers were observed, and the minor diameter (D) of 100 randomly selected cellulose fibers was measured, and the arithmetic average of the 100 cellulose fibers was calculated.

[0200] [Specific surface area] Approximately 0.2 g of the porous sheet was dried under vacuum at 120°C for 5 hours using a surface area and pore size distribution analyzer (Nova-4200e, manufactured by Quantachrome Instruments). The amount of nitrogen gas adsorbed at the boiling point of liquid nitrogen was then measured at 5 points in the range of relative vapor pressure (P / P0) between 0.05 and 0.2 (multipoint method). The BET surface area (m 2 / g) was calculated.

[0201] [Acyl Substitution Degree DS] The infrared spectrum of the porous sheet at five points was measured by the ATR-IR method using a Fourier transform infrared spectrophotometer (FT / IR-6200 manufactured by JASCO Co., Ltd.) The infrared spectrum measurement was performed under the following conditions. Accumulation count: 64 times, Wavenumber resolution: 4cm -1 , Measurement wave number range: 4000~600cm -1 , ATR crystal: Diamond, Incident angle: 45°

[0202] From the obtained IR spectrum, the IR index was calculated according to the following formula: IR index = H1730 / H1030 In the formula, H1730 and H1030 are at 1730 cm -1 , 1030cm -1(absorption band of CO stretching vibration of cellulose backbone chain) -1 and 1500cm -1 The line connecting the -1 and 1500cm -1 The line connecting these points is taken as the baseline, and the absorbance is calculated when this baseline is taken as 0. The average degree of substitution at each measurement site was calculated from the IR index according to the following formula, and the average value was taken as DS. DS = 4.13 × IR index

[0203] [DS heterogeneity ratio (CV)] The porous sheet that had been subjected to the ATR-IR measurement was frozen and crushed to prepare a powder sample of cellulose. The powder was placed on 10 2.5 mm diameter dish-shaped sample stands, the surface was pressed down to make it flat, and each was subjected to XPS measurement. Peak separation was performed on the obtained C1s spectrum, and the DSs of each sample was calculated using the area intensity (Ixf) of the peak (286 eV) derived from the OC=O bond of the acetyl group relative to the area intensity (Ixp) of the peak (289 eV, CC bond) attributed to the carbons C2-C6 derived from the pyranose ring of cellulose, and the average was taken as the DSs of the cellulose fiber. DSs = (Ixf) x 5 / (Ixp)

[0204] The conditions used for the XPS measurement are as follows: Equipment used: ULVAC-Phi VersaProbe II Excitation source: mono.AlKα 15kV×3.33mA Analysis size: Approx. 200 μm φ Photoelectron extraction angle: 45° Capture Area Narrow scan: C 1s, O 1s Pass Energy: 23.5eV

[0205] Based on the above DS and DSs, the DS heterogeneity ratio (CV) was calculated according to the following formula. DS heterogeneity ratio (CV) = DSs / DS

[0206] [Thermal decomposition onset temperature (T D )] The thermal analysis of the porous sheet was carried out by the following measurement method. Equipment: Rigaku Thermo plus EVO2 Sample: 10 mg of circular samples were cut out from the porous sheet and placed in an aluminum sample pan. Sample size: 10mg Measurement conditions: In a nitrogen flow of 100 ml / min, the temperature was increased from room temperature to 150°C at a rate of 10°C / min, and then held at 150°C for 1 hour, after which the temperature was increased to 450°C at a rate of 10°C / min. T D Calculation method: Calculated from a graph with temperature on the horizontal axis and weight remaining rate % on the vertical axis. Starting from the weight (weight loss 0 wt%) of the porous sheet at 150°C (state where moisture is almost completely removed), the temperature was further increased, and a straight line was obtained that passed through the temperatures at 1 wt% weight loss and 2 wt% weight loss. The temperature at the point where this straight line intersects with the horizontal line (baseline) that passes through the starting point of 0 wt% weight loss was determined as the thermal decomposition onset temperature (T D ) was decided.

[0207] [1wt% weight loss temperature] Said T D The temperature at which the weight loss reached 1 wt% was calculated was taken as the 1 wt% weight loss temperature.

[0208] [Weight change rate at 250℃] Equipment: Rigaku Thermo plus EVO2 Sample: 10 mg of circular samples were cut out from the porous sheet and placed in an aluminum sample pan. Sample size: 10mg Measurement conditions: In a nitrogen flow of 100 ml / min, the temperature was increased from room temperature to 150°C at a rate of 10°C / min, and then held at 150°C for 1 hour. The temperature was then increased from 150°C to 250°C at a rate of 10°C / min, and held at 250°C for 2 hours. The weight W0 at the time when 250°C was reached was taken as the starting point, and the weight W1 after holding at 250°C for 2 hours was calculated using the following formula. Weight change rate at 250℃ (%): (W1-W0) / W0×100

[0209] <Polyphenylene ether> [Weight average molecular weight] A gel permeation chromatograph (Shimadzu Corporation, LC-2030C Plus) was used as a measuring device, and a calibration curve was prepared using standard polystyrene and ethylbenzene. The weight average molecular weight (Mw) of the modified polyphenylene ether obtained was measured using this calibration curve. Standard polystyrenes with molecular weights of 3,650,000, 2,170,000, 1,090,000, 681,000, 204,000, 52,000, 30,200, 13,800, 3,360, 1,300, and 550 were used.

[0210] The column used was two Showa Denko K-805L columns connected in series. The solvent used was chloroform, the solvent flow rate was 1.0 mL / min, and the column temperature was 40°C. A 1 g / L chloroform solution of polyphenylene ether was prepared and used as the measurement sample. The UV wavelength of the detection unit was 254 nm for standard polystyrene and 283 nm for polyphenylene ether. The weight average molecular weight was calculated from the peak area ratio based on the curve showing the molecular weight distribution obtained by GPC based on the above measurement data.

[0211] [Viscosity of polyphenylene ether and dispersant at 23°C] The viscosity of the polyphenylene ether and the dispersant was measured using a B-type viscometer (manufactured by Eiko Seiki Co., Ltd., model number DVNext) at a rotation speed of 10 rpm.

[0212] [Viscosity of polyphenylene ether and dispersant at 80℃] The jacket temperature of the Brookfield viscometer was adjusted to 80° C., and the measurement was performed at a rotation speed of 10 rpm.

[0213] [Amount of vinyl and aromatic styrene in dispersant] The values ​​listed in the supplier's product catalogue are given in Table 2.

[0214] [Glass transition temperature of polyphenylene ether and dispersant] The glass transition temperature of polyphenylene ether was measured using a differential scanning calorimeter DSC250 (TA Instruments). In a nitrogen atmosphere, the sample was heated from -90 to 30°C at a heating rate of 10°C per minute, then cooled to -90°C at a heating rate of 20°C per minute, and the glass transition temperature was then measured at a heating rate of 10°C per minute. The glass transition temperature of the dispersant is based on the supplier's product catalog.

[0215] [Thermal decomposition temperature of polyphenylene ether and dispersant (5% weight loss temperature)] Thermal analysis of the polymer samples was carried out by the following measurement methods. Equipment: HITACHI simultaneous differential thermogravimetry measurement equipment (TG / DTA) STA7200RV Samples: Polymer samples were placed in aluminum sample pans. Sample size: 10mg Measurement conditions: In nitrogen, the temperature was increased from 30° C. to 550° C. at a rate of 20° C. / min, and the temperature was maintained at 550° C. for 10 minutes. T D Calculation method: 5% weight loss temperature is the thermal decomposition start temperature (T D ) was decided.

[0216] <Resin composition> [Confirmation of whether low Tg polyphenylene ether exists between cellulose nanofiber and resin] The evaluation was carried out using a scanning transmission electron microscope (STEM) under the following conditions. The resin composition pellet was trimmed to an appropriate size, and an ultrathin section of the MD-ND cross section was prepared at a set thickness of 100 nm using a cryomicrotome. After loading this on a copper mesh, appropriate staining was applied from electronic staining such as ruthenium staining, osmium staining, and phosphotungstic acid staining to obtain a specimen for microscopy. The observation conditions for STEM were as follows. Equipment: S-5500 (Hitachi, Ltd.) Accelerating voltage: 30.0 kV Detector: BF-STEM (transmitted image) In the obtained transmission images, those having a fibrous shape were regarded as cellulose nanofibers, and the following observations were made to determine whether low Tg polyphenylene ether was present at the interface between the cellulose nanofibers and the resin. Ten images were taken at a magnification of 50,000 times in an arbitrary field of view, and the case where low Tg polyphenylene ether was present at the interface in all images was judged as "present," and the case where low Tg polyphenylene ether was not observed at the interface in some or all of the images was judged as "absent."

[0217] [Weight loss rate of resin composition at 250°C] For the examples in which the thermoplastic resin was polyamide, the weight loss rate was measured in the same manner as for the cellulose nanofibers. For the examples in which the thermoplastic resin was polypropylene or polyacetal, the weight loss rate was not measured because these resins decompose at 250°C or lower.

[0218] [Tensile yield strength and tensile elongation at break] Tensile strength at yield and elongation at break were measured according to ISO 527-1. For molded pieces that broke before yielding, the maximum strength was used instead.

[0219] [Flexural modulus] The obtained pellets were molded using an injection molding machine under conditions conforming to JIS K6920-2 to mold multipurpose test pieces conforming to ISO294-3. The molding temperatures for injection molding were 260°C for polyamide 6, 200°C for polypropylene, and 210°C for polyacetal. The flexural modulus was measured in accordance with ISO179. Since polyamide resin changes due to moisture absorption, it was stored in an aluminum moisture-proof bag immediately after molding to suppress moisture absorption.

[0220] [Linear expansion coefficient] A cubic sample measuring 4 mm in length, 4 mm in width and 4 mm in length was cut out from the center of the multipurpose test piece using a precision cut-off saw, and measurements were performed in accordance with ISO11359-2 at temperatures ranging from -20°C to 80°C, and the expansion coefficient between 0°C and 60°C was calculated. Prior to the measurements, the sample was left to stand in a 120°C environment for 2 hours for annealing.

[0221] [Void] The center of the multipurpose test piece was cut from the center line in the direction of resin flow, and the presence or absence of voids (air gaps) of 0.3 mm or more was observed under an optical microscope (10x magnification) and evaluated according to the following criteria. ○: No voids were detected. ×: The presence of voids was confirmed.

[0222] [Sliding characteristics] The gripping part of a molded piece injection-molded into the shape of an ISO multipurpose test piece was used as the disk part to evaluate the ball-on-disk friction coefficient and sliding properties against SUS.Specifically, a ball-on-disk type reciprocating friction and wear tester (AFT-15MS type, manufactured by Toyo Seimitsu Co., Ltd.) was used to perform a sliding test of 20,000 reciprocating cycles using a SUS ball with a diameter of 5 mm at a load of 9.8 N, a linear velocity of 30 mm / sec, and a reciprocating distance of 20 mm, in an environment of 23°C and 50% humidity.The generation of rubbing noise was evaluated according to the following evaluation criteria. : Almost no scraping noise was heard until the end (20,000 strokes). ○: Initially (approximately less than 500 strokes), there was a scraping noise, but it stopped afterwards. △: There was constant scraping noise and wear was observed. ×: There was constant scraping noise, severe wear, and a large amount of wear powder was generated.

[0223] ≪Materials used≫ <Cellulose nanofiber> CNF-A: Acetylated cellulose nanofiber 3 parts by mass of cotton linter pulp was immersed in 27 parts by mass of water and dispersed with a pulper. 30 parts by mass of the pulper-treated cotton linter pulp slurry (including 3 parts by mass of cotton linter pulp) was added to 170 parts by mass of water to disperse the mixture in water (solid content: 1.5% by mass), and the aqueous dispersion was beaten for 30 minutes using a SDR14 lab refiner (pressure type disk type) manufactured by Aikawa Iron Works Co., Ltd. as a disk refiner device with a clearance between disks of 1 mm. Subsequently, thorough beating was performed under conditions in which the clearance was reduced to a level close to zero, to obtain a beaten aqueous dispersion (solid content concentration: 1.5% by mass). The obtained beaten aqueous dispersion was directly subjected to a high-pressure homogenizer (NSO15H manufactured by Niro Soavi Co., Ltd. (Italy)) for 10 times of refinement under an operating pressure of 100 MPa to obtain a slurry (solid content concentration: 1.5% by mass). The mixture was then concentrated to a solid content of 20% by mass using a dehydrator, yielding 15 parts by mass of a concentrated cake.

[0224] 5 parts by mass of the concentrated cake (solid content rate 20% by mass) and 95 parts by mass of DMSO were added to a KAPPA VITA (registered trademark) homomixer (tank size 35 L) manufactured by NETZSCH Vakumix, and dispersed at 2500 rpm (circumferential speed 12 m / s) of the homomixer, and 100 parts by mass of DMSO slurry (solid content rate 1.0% by mass) was obtained. Then, 2 parts by mass of vinyl acetate and 0.3 parts by mass of potassium carbonate were added and stirred at 40°C for 3 hours. To stop the reaction, 100 parts by mass of water were added while stirring. Then, the solid content was filtered off by filtration. 100 parts by mass of water was added to the obtained solid content, and the solid content was dispersed in a homomixer, and a washing operation of filtering was performed six times to obtain 5 parts by mass of CNF-A concentrated cake (solid content rate 20% by mass).

[0225] CNF-B: Commercially available cellulose nanofiber Commercially available Celish KY100G (manufactured by Daicel Finechem) was used as the CNF-B cake.

[0226] The properties of the cellulose nanofibers are shown in Table 1.

[0227] [Table 1]

[0228] <Resin> Polyamide 6 (UBE NYLON 1013B, manufactured by Ube Industries, Ltd.), melting point: 225°C Polyacetal-1 (TENAC HC450, Asahi Kasei Corporation), melting point: 165°C Polyacetal-2 (TENAC 4010, Asahi Kasei Corporation), melting point: 175°C Polypropylene (Prime Polymer Co., Ltd., J106G), melting point: 160°C

[0229] <Polyphenylene ether> The modified cardanol synthesized by the method of Production Example 1 below was used to obtain polyphenylene ethers by the methods of Production Examples 2 to 7 below.

[0230] (Production Example 1) Synthesis of Modified Cardanol Cardanol (product name NX-2026, manufactured by Cardolite, 345 g) and p-toluenesulfonic acid monohydrate (5.9 g) were added in sequence to a 1 L flask connected to a Dewar condenser at -10°C, and stirred with a stirring blade. Then, the external temperature was set to 80°C using an aluminum block heating device and heated. Isobutene (100 g) was gradually introduced over 10 hours. The supply of isobutene was stopped, and then stirring was continued at 80°C for 15 hours. The temperature of the reaction solution was lowered to 40°C, and toluene (300 g) was added to the reaction solution. Furthermore, a 5% aqueous sodium hydroxide solution (27 g) was dropped. Ion-exchanged water (320 g) was added, the temperature of the reaction solution was raised to 70°C, and after stirring for 30 minutes, the organic layer was collected using a separatory funnel. Ion-exchanged water (760 g) was added to the collected organic layer, the temperature of the reaction solution was raised to 70° C., and the mixture was stirred for 30 minutes and then allowed to stand. The organic layer was collected using a separatory funnel. The washed organic layer was concentrated using a rotary evaporator to obtain a pale yellow oily modified cardanol (370 g).

[0231] The structure of the obtained compound was identified as follows: 1H-NMR was performed under the following conditions. Equipment :JEOL JNM-ECZ500 Frequency: 500MHz Number of times: 256 Solvent: deuterated chloroform Concentration: 8 mg of sample dissolved in 0.6 mL of deuterated chloroform As a result, it was found that the main component was cardanol with a tert-butyl group introduced at the 2-position of the cardanol raw material before the reaction.

[0232] Cardanol Source: 1 H-NMR(CDCl3) δ 7.15-7.10(m,1H),6.78-6.73(m,1H),6.68-6.62(m,2H),5.88-5.77(m,0.37H),5.50-5.29(m,3.44H),5.10-4.95(m,0.80H),4.81-4.64( m,1H),2.88-2.75(m,2.14H),2.55(t,2.13H),2.08-1.98(m,3.31H),1.69-1.53(m,3.15H),1.51-1.12(m,14.10H),0.94-0.85(m,1.95H) Modified Cardanol (Product): 1 H-NMR(CDCl3) δ 7.16(d,1H),6.69(dd,1H),6.49(d,1H),5.88-5.77(m,0.39H),5.50-5.29(m,3.56H),5.10-4.95(m,0.80H),4.64(s,1H),2.87- 2.75(m,2.12H),2.56-2.46(m,2.22H),2.12-1.95(m,3.60),1.65-1.53(m,2.62H),1.43-1.24(m,23.42H),0.96-0.80(m,2.20H)

[0233] (Production Example 2) Synthesis of polyphenylene ether 1 (PPE1) A 1.0-liter jacketed reactor equipped with a line for introducing nitrogen gas at the top of the reactor, a sparger for introducing oxygen-containing gas at the bottom of the reactor, stirring turbine blades and baffles, and a reflux condenser on the vent gas line at the top of the reactor was charged with a mixture of 0.033 g of cuprous oxide and 0.248 g of 47% hydrogen bromide, 0.079 g of N,N'-di-t-butylethylenediamine, 1.17 g of dimethyl-n-butylamine, 0.38 g of di-n-butylamine, 6.40 g of 2,6-dimethylphenol, 43.6 g of modified cardanol, 0.05 g of methyltri-n-octylammonium chloride, and 448 g of toluene, while flowing nitrogen gas at a rate of 0.77 L / min. Then, air was introduced into the reactor from the sparger at a rate of 0.53 L / min while vigorously stirring. The polymerization temperature was adjusted by passing a heat medium through the jacket to maintain it at 40°C. 120 minutes after the start of air introduction, the air flow was stopped, the inside of the reactor was replaced with nitrogen gas, and then 0.35 g of ethylenediaminetetraacetic acid tetrasodium salt tetrahydrate (a reagent manufactured by Dojindo Laboratories) was added as an aqueous solution of 50 g of water. The mixture was heated to 70°C, and copper extraction was carried out at 70°C for 3 hours. Thereafter, the mixture was separated by standing to separate into a polyphenylene ether solution (organic phase) and an aqueous phase to which the catalyst metal had been transferred. The solvent of the organic phase was removed by a rotary evaporator. The polyphenylene ether thus obtained was subjected to the respective measurements by the methods described above. The results of the respective analyses are shown in Table 2.

[0234] (Production Example 3) Synthesis of polyphenylene ether 2 (PPE2) A polyphenylene ether was obtained in the same manner as in Production Example 2, except that 12.75 g of 2,6-dimethylphenol and 37.25 g of modified cardanol were used. The polyphenylene ether thus obtained was subjected to the respective measurements by the methods described above. The results of the respective analyses are shown in Table 2.

[0235] (Production Example 4) Synthesis of polyphenylene ether 3 (PPE3) A polyphenylene ether was obtained in the same manner as in Production Example 2, except that 9.29 g of 2,6-dimethylphenol and 40.71 g of modified cardanol were used. The polyphenylene ether thus obtained was subjected to the respective measurements by the methods described above. The results of the respective analyses are shown in Table 2.

[0236] (Production Example 5) Synthesis of polyphenylene ether 4 (PPE4) A polyphenylene ether was obtained in the same manner as in Production Example 2, except that 3.94 g of 2,6-dimethylphenol and 46.06 g of modified cardanol were used. The polyphenylene ether thus obtained was subjected to the respective measurements by the methods described above. The results of the respective analyses are shown in Table 2.

[0237] (Production Example 6) Synthesis of polyphenylene ether 5 (PPE5) A polyphenylene ether was obtained in the same manner as in Production Example 2, except that 16.96 g of 2,6-dimethylphenol and 33.04 g of modified cardanol were used. The polyphenylene ether thus obtained was subjected to the respective measurements by the methods described above. The results of the respective analyses are shown in Table 2.

[0238] (Production Example 7) Synthesis of polyphenylene ether 6 (PPE6) A polyphenylene ether was obtained in the same manner as in Production Example 2, except that 22.20 g of 2,6-dimethylphenol and 27.80 g of modified cardanol were used. The polyphenylene ether thus obtained was subjected to the respective measurements by the methods described above. The results of the respective analyses are shown in Table 2.

[0239] [Table 2]

[0240] <Dispersant> Dispersant-1: Ethylene oxide propylene oxide copolymer shown in Table 2 Dispersant-2: Polyoxyethylene as shown in Table 2 Dispersant-3: butadiene-styrene random copolymer shown in Table 2 (Note that the number average molecular weight Mn values ​​in Table 2 are based on the supplier's product catalog.)

[0241] <Additional Ingredients> Antioxidant: BASF, Irganox 245

[0242] <Preparation of resin composition> [Examples 1 to 18] The above materials were used in the compositions shown in Tables 3 and 4, and resin compositions were prepared according to the following procedure.

[0243] The cellulose cake, polyphenylene ether, and antioxidant were mixed in the proportions shown in Tables 3 and 4 and dried under reduced pressure using a planetary mixer to obtain a dried cellulose product. The above-mentioned dried cellulose and resin were blended in the ratios shown in Tables 3 and 4, and kneaded in a twin-screw extruder to obtain cellulose-containing resin pellets as a resin composition.

[0244] [Comparative Examples 1 to 11] Resin compositions were obtained in the same manner as in Example 1, except that in the formulations shown in Tables 3 and 4, a dispersing agent was used instead of polyphenylene ether. The evaluation results are shown in Tables 3 and 4.

[0245] [Table 3]

[0246] [Table 4]

[0247] [Example 19] A profile extrusion molding was carried out using the resin composition pellets of Example 1. Using a single screw extruder with a diameter of 40 mm equipped with a die having a cross-sectional shape shown in Fig. 1 (the numerical values ​​in the figure are in millimeters), the pellets were extruded at a molding temperature of 250°C and a screw rotation speed of 20 rpm, and then shaped using a sizing die having the same cross section as the die in a 2 m long water tank filled with cooling water at a water temperature of 25°C, to obtain a profile extrusion molded product. Profile extrusion molding was possible without any problems.

[0248] [Example 20] The resin composition pellets of Example 8 were used for irregular extrusion molding. Using a 40 mm diameter single screw extruder equipped with a die having a cross-sectional shape shown in Figure 1, the pellets were extruded at a molding temperature of 200°C and a screw rotation speed of 20 rpm, and then shaped using a sizing die having the same cross section as the die in a 2 m long water tank filled with cooling water at a water temperature of 25°C to obtain an irregular extrusion molded product. The irregular extrusion molding was possible without any problems.

[0249] [Example 21] The resin composition pellets of Example 14 were used for irregular extrusion molding. Using a 40 mm diameter single screw extruder equipped with a die having a cross-sectional shape shown in Figure 1, the pellets were extruded at a molding temperature of 190°C and a screw rotation speed of 20 rpm, and then shaped using a sizing die having the same cross section as the die in a 2 m long water tank containing cooling water at a water temperature of 25°C to obtain an irregular extrusion molded product. The irregular extrusion molding was possible without any problems. [Industrial Applicability]

[0250] The resin composition according to the present invention can be suitably applied to various applications of resin molded products.

Claims

1. A resin composition comprising cellulose nanofibers, a thermoplastic resin, and a polyphenylene ether having a glass transition temperature of -100°C to 50°C as measured by differential scanning calorimetry (DSC).

2. 2. The resin composition according to claim 1, wherein the polyphenylene ether has a saturated or unsaturated hydrocarbon group having 7 to 25 carbon atoms which may be substituted.

3. 2. The resin composition according to claim 1, wherein the polyphenylene ether contains a repeating unit derived from a phenol compound represented by the following formula (1): 【Chemistry 1】 (In formula (1), R 13 is an optionally substituted saturated or unsaturated hydrocarbon group having 15 carbon atoms, R 11 and R 12 are each independently a hydrogen atom, a linear saturated hydrocarbon group having 1 to 12 carbon atoms, or a substituent represented by the following formula (1-1), where R 11 and R 12 None of the atoms can be hydrogen atoms.) 【Chemistry 2】 (In formula (1-1), R 31 are each independently a linear alkyl group having 1 to 8 carbon atoms which may be substituted, or two R 31 The atoms in R are bonded to each other to form a cyclic alkyl group having 1 to 8 carbon atoms. 32 each independently represents an optionally substituted alkylene group having 1 to 8 carbon atoms; each b independently represents 0 or 1; R 33 is a hydrogen atom, an optionally substituted alkyl group having 1 to 8 carbon atoms, or an optionally substituted phenyl group.

4. R in the above formula (1) 11 is a substituent represented by the formula (1-1).

5. The resin composition according to claim 3, wherein the substituent represented by the formula (1-1) is a t-butyl group.

6. The resin composition according to claim 1, wherein the polyphenylene ether has a weight average molecular weight of 1,000 to 150,000.

7. The resin composition according to claim 1, wherein the polyphenylene ether has a viscosity at 80° C. of 1 mPa·s to 1,000,000 mPa·s.

8. The resin composition according to claim 1 , wherein the polyphenylene ether has a thermal decomposition onset temperature of 300° C. or higher.

9. The resin composition according to claim 1 , wherein the cellulose nanofiber is a chemically modified cellulose nanofiber.

10. The resin composition according to claim 9, wherein the chemically modified cellulose nanofiber is an acylated cellulose nanofiber having an acyl substitution degree of 0.1 to 2.

0.

11. The resin composition according to claim 1, wherein the cellulose nanofibers have a number average fiber diameter of 2 nm to 1000 nm.

12. The resin composition according to claim 1, wherein the cellulose nanofibers have a thermal decomposition onset temperature of 250° C. or higher.

13. The resin composition according to claim 1 , wherein the polyphenylene ether is present in a form infiltrating at least a portion of the interface between the cellulose nanofibers and the thermoplastic resin.

14. The resin composition according to claim 1 , wherein the resin composition has a weight loss rate at 250° C. of 1.5% or less.

15. The thermal decomposition onset temperature T1 of the polyphenylene ether and the thermal decomposition onset temperature T2 of the cellulose nanofibers have the following relationship: (T1) ≧ (T2) The resin composition according to claim 1, which satisfies the above.

16. The resin composition according to claim 15, wherein the difference T1-T2 between T1 and T2 is 5°C or more.

17. The resin composition according to claim 1 , wherein the thermoplastic resin is at least one selected from the group consisting of polyamide-based resins, polyolefin-based resins, and polyacetal-based resins.

18. The thermal decomposition starting temperature T1 of the polyphenylene ether and the temperature T3 which is the melting point or the glass transition temperature + 70° C. of the thermoplastic resin satisfy the following relationship: (T1)>(T3) The resin composition according to claim 1, which satisfies the above.

19. The resin composition according to claim 18, wherein the thermoplastic resin is a crystalline thermoplastic resin, and the temperature T3 is a melting point of the thermoplastic resin.

20. The thermal decomposition starting temperature T1 of the polyphenylene ether and the temperature T4 which is the melting point or the glass transition temperature + 100° C. of the thermoplastic resin satisfy the following relationship: (T1)>(T4) The resin composition according to claim 1, which satisfies the above.

21. The resin composition according to claim 1, which is free of a surfactant.

22. A dried body comprising cellulose nanofibers and a polyphenylene ether having a glass transition temperature of -100°C to 50°C as measured by differential scanning calorimetry (DSC).

23. A method for producing the resin composition according to any one of claims 1 to 21, The method includes heating and kneading a mixture containing cellulose nanofibers, a thermoplastic resin, and a polyphenylene ether having a glass transition temperature of -100°C to 50°C as measured by differential scanning calorimetry (DSC).

24. A dried body containing cellulose nanofibers and polyphenylene ether having a glass transition temperature of −100° C. to 50° C. as measured by differential scanning calorimetry (DSC); A thermoplastic resin; 24. The method of claim 23, wherein the mixture is obtained by mixing

25. A molded article obtained by molding the resin composition according to any one of claims 1 to 21.

26. 26. The molded article of claim 25 which is a profile extrusion.

27. A method for producing a profile extrusion product, comprising: A method comprising the step of profile extruding the resin composition of any one of claims 1 to 21.

28. A 3D printing modeling material comprising the resin composition according to claim 1.

29. 30. The 3D printing modeling material of claim 28, having the form of a filament or a powder.

30. A molded object obtained by molding the resin composition according to any one of claims 1 to 21 or the 3D printing material according to claim 28 or 29 using a 3D printer.

31. A method for manufacturing a shaped object, comprising the steps of: A method comprising a step of modeling the resin composition according to any one of claims 1 to 21 or the 3D printing modeling material according to claim 28 or 29 using a 3D printer.

Citation Information

Patent Citations

  • Dispersion and cellulose-containing composition

    JP2020063408A

Cited By

  • Rubber composition and method for using polyphenylene ether

    WO2025127084A1